Regeneration treatment method and application of degradable high polymer material

By using specific organic non-metallic catalysts in the aqueous solvent system to degrade the degradable polymer materials, the problems of slow reaction speed and low conversion rate in the prior art are solved, and efficient resource recovery and environmental protection effects are achieved.

CN119263974APending Publication Date: 2025-01-07FUDAN UNIVERSITY

Patent Information

Application Number
CN202310821769.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively degrade and recover degradable polymer materials. The traditional methods have slow reaction speed, low conversion rate, and serious environmental pollution problems.

Method used

The degradable polymer materials are degraded in an aqueous solvent system using organic non-metallic catalysts of specific structures, such as diphenyl phosphate and binaphthol phosphate, to obtain a low molecular weight composition for regeneration and recovery.

Benefits of technology

The rapid degradation and high conversion of degradable polymer materials are achieved, the degradable product polymerization is low, the post-treatment steps are simplified, the cost and environmental pollution are reduced, and the recycling of resources is promoted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263974A_ABST
    Figure CN119263974A_ABST
Patent Text Reader

Abstract

The invention relates to a regeneration treatment method and application of a degradable high polymer material, and the regeneration treatment method comprises the following steps: degrading the degradable high polymer material in a system in which an organic nonmetal catalyst and a water-containing solvent exist to obtain a degradation product; wherein the degradable high polymer material comprises one or more of a polyester material and a polycarbonate material; the organic nonmetal catalyst is selected from one or more of diphenyl phosphate, binaphthol phosphate and organic alkali. By adopting the specific organic non-metal catalyst, efficient degradation of the degradable high polymer material can be realized, the degradation speed is high, the conversion rate is high, the reaction yield is high, and the cost is low; degradation products can be effectively utilized again as valuable chemicals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer material recycling, and in particular to a regeneration method and application of a degradable polymer material. Background Art

[0002] With the continuous increase in the output and consumption of polymer materials at home and abroad, the recycling of polymer materials has become the key to the sustainable development of the industry. Degradable polymer materials have received widespread attention due to their inherent characteristics of being degradable under specific conditions, especially polylactic acid, polycaprolactone, polybutylene adipate / terephthalate, etc. As environmentally friendly materials, they have replaced some traditional polymer materials (polyethylene terephthalate, polyvinyl chloride, polypropylene, etc.) in the market and are widely used in packaging and medicine, etc., in order to reduce the pollution caused by polymer materials to the environment.

[0003] The natural degradation rate of degradable polymer materials (such as polyester, polycarbonate, etc.) is slow. It takes two to three years to degrade to a low molecular state in the ocean and soil. Even under industrial composting conditions, it takes about half a year to completely degrade. The uneven natural degradation rate of degradable polymer materials will form broken plastic particles rather than oligomers. The microplastic problem caused is even more serious than that of petroleum-based plastics. Not only can the recycling of resources not be achieved, but it will also cause secondary pollution to the environment. At the same time, traditional recycling methods such as thermal cracking, alcoholysis and hydrolysis have harsh processing conditions, small single processing volume and slow processing speed. The degradation products need to undergo cumbersome purification steps before they can be effectively reused. Summary of the invention

[0004] Based on this, the purpose of the present invention includes providing a regeneration method for degradable polymer materials, using a low-cost specific catalyst to achieve efficient degradation of degradable polymer materials, the method not only has a fast degradation rate, but also a high conversion rate and a high reaction yield. The present application also provides an application using the regeneration method.

[0005] In a first aspect of the present application, a method for regenerating a degradable polymer material is provided, comprising the following steps: degrading the degradable polymer material in a system in which an organic non-metallic catalyst and an aqueous solvent exist to obtain a degradation product;

[0006] in,

[0007] The degradable polymer material includes one or more of polyester material and polycarbonate material;

[0008] The organic non-metal catalyst is selected from one or more of diphenyl phosphate, binaphthol phosphate and organic bases, and the organic base is selected from one or more of nitrogen-containing heterobicyclic bases, 4-dimethylaminopyridine and phosphazene base compounds.

[0009] In some embodiments, in the regeneration method, the diphenyl phosphate has a structure shown in formula (I):

[0010]

[0011] In formula (I), R 11 , R 12 , R 13 , R 14 , R 15 , R 21 , R 22 , R 23 , R 24 and R 25 are each independently selected from -H, halogen, -NO 2 , C 1 ~C 4 Alkoxy, C 1 ~C 6 Alkyl, halogen substituted C 1 ~C 6 any one of an alkyl group, a phenyl group, and a substituted phenyl group, wherein the phenyl ring in the substituted phenyl group is substituted by one or more substituents selected from the group consisting of halogen and C 1 ~C 4 alkyl;

[0012] The binaphthol phosphate has a structure shown in formula (II):

[0013]

[0014] In formula (II), R 3 and R 3 ' can be independently selected from -H, -SiPh 3 or Wherein, “*” indicates the attachment site of a covalent single bond;

[0015] R 41 , R 42 , R 43 , R 44 and R 45 are each independently selected from -H, halogen, -NO 2 , C 1 ~C 6 Alkyl, halogen substituted C 1 ~C 6any one of an alkyl group, a phenyl group, and a substituted phenyl group, wherein the phenyl ring in the substituted phenyl group is substituted by one or more substituents selected from the group consisting of halogen, -NO 2 , phenyl and C 1 ~C 4 Alkyl; or R 41 , R 42 , R 43 , R 44 and R 45 At least two of them form a ring and participate in forming a fused ring, R 41 , R 42 , R 43 , R 44 and R 45 The non-cyclic groups are each independently selected from -H, halogen, -NO 2 , C 1 ~C 6 Alkyl, halogen substituted C 1 ~C 6 any one of an alkyl group, a phenyl group, and a substituted phenyl group, wherein the phenyl ring in the substituted phenyl group is substituted by one or more substituents selected from the group consisting of halogen, -NO 2 , phenyl and C 1 ~C 4 alkyl;

[0016] The nitrogen-containing heterobicyclic base is selected from the group consisting of:

[0017]

[0018] In formula (III), Y is -CH 2 -, -NH- or -N(CH 3 )-; n is 1 or 2;

[0019] The phosphazene base compound has a structure shown in formula (IV):

[0020]

[0021] In formula (IV), R is halogen, C 1 ~C 4 Alkyl or C 1 ~C 4 Alkoxy.

[0022] In some embodiments, the regeneration method satisfies one or more of the following characteristics:

[0023] The number average molecular weight of the degradable polymer material is 10 kDa to 250 kDa;

[0024] The mass ratio of water to the degradable polymer material in the system is (0.01-10):1;

[0025] The mass ratio of the organic non-metallic catalyst to the degradable polymer material is (0.001-0.1):1;

[0026] The average degree of polymerization of the degradation product is ≤20.

[0027] In some embodiments, the regeneration method satisfies one or more of the following characteristics:

[0028] The degradable polymer material is selected from one or more of polylactic acid, polyglycolic acid, polyε-caprolactone, polylactic acid-glycolic acid copolymer, polyglycolic acid-ε-caprolactone copolymer, polylactic acid-ε-caprolactone copolymer, polyδ-valerolactone, polybutyrolactone, polybutylene succinate, polybutylene adipate / terephthalate, polyhydroxyalkanoate and polytrimethylene carbonate;

[0029] The diphenyl phosphate catalyst is selected from one or more of diphenyl phosphate, bis(4-nitrophenyl)phosphate and bis(2,6-dimethylphenyl)phosphate;

[0030] The binaphthol phosphate catalyst is one or more of binaphthol phosphate, R-binaphthol phosphate, R-3,3'-bis(triphenylsilyl)binaphthol phosphonate and R-3,3'-bis(2,4,6-triisopropylphenyl)binaphthol phosphonate;

[0031] The organic base catalyst is selected from 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,5,7-triazidobicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 4-dimethylaminopyridine, tert-butylimino-tris(dimethylamino)phosphorane, 1-tert-butyl-2,2,4,4,4-penta(dimethylamino)-2Λ5,4Λ5-bis(phosphorus nitrogen-based compound) and cyclotriphosphazene base and 1-tert-butyl-4,4,4-tris(dimethylamino)-2,2-bis[tris(dimethylamino)-phosphoranylideneamino]-2Λ5,4Λ5-bis(phosphorus nitrogen-based compound) One or more.

[0032] In some embodiments, the regeneration method comprises the following steps: performing a first degradation treatment on the first degradable polymer material in a system in which the organic non-metallic catalyst and the aqueous solvent exist to obtain a first degradation product;

[0033] The i-th degradation product and the i+1-th degradable polymer material are mixed, and the i+1-th degradation treatment is performed to obtain the i+1-th degradation product, wherein i is an integer ≥1, and the i+1-th degradable polymer material includes at least the second degradable polymer material; the degradation treatment is terminated when i+1=n to obtain the n-th degradation product, wherein n is an integer ≥2, and the average degree of polymerization of the n-th degradation product is ≤20.

[0034] In some embodiments, the regeneration method satisfies one or more of the following characteristics:

[0035] The temperature of any degradation treatment is independently 125°C to 200°C;

[0036] The time of any degradation treatment is independently 0.25h to 5h;

[0037] The pressure of any degradation treatment is independently 100±5 kPa.

[0038] In some embodiments, the regeneration method further includes the following steps: washing the degradation product with an organic solvent; wherein the organic solvent is selected from one or more of chloroform, petroleum ether, carbon disulfide, ether, dichloromethane, benzene, toluene and ethyl acetate.

[0039] The second aspect of the present application provides a low molecular weight composition, which is a degradation product of a degradable polymer material, and the low molecular weight composition is prepared according to the regeneration method described in the first aspect, wherein the average degree of polymerization of the low molecular weight composition is ≤20.

[0040] The third aspect of the present application provides a method for recycling degradable polymer materials, comprising the following steps: conducting a polymerization reaction using a low molecular weight composition as an initial raw material; wherein the low molecular weight composition is a degradation product prepared by the regeneration method described in the first aspect or the low molecular weight composition described in the second aspect.

[0041] In a fourth aspect of the present application, there is provided an application of an organic non-metallic catalyst in the degradation treatment of a degradable polymer material;

[0042] Wherein, the organic non-metallic catalyst and the degradable polymer material are as defined in the first aspect.

[0043] The present application adopts a specific organic non-metallic catalyst to regenerate and recycle degradable polymer materials. The specific organic non-metallic catalyst used has been screened through a large number of experiments and found to be able to efficiently catalyze the hydrolysis of degradable polymer materials such as polyester and polycarbonate. In the regeneration treatment method of degradable polymer materials provided by the present application, the conversion rate of degradable polymer materials is high, the degree of polymerization of degradation products is low (for example, monomers or close to monomer levels can be obtained), and the low molecular weight composition in the system after the degradation reaction can achieve a high proportion (for example, more than 95%). In addition, the post-processing operation is simple, the recovery efficiency is high, the process is green and environmentally friendly, and the cost is low.

[0044] In the regeneration treatment method of the degradable polymer material provided in the present application, the catalytic degradation process of the degradable polymer material can be carried out at normal pressure and relatively low temperature, without involving organic solvents, and without the need for strong acid or strong alkali environment, not only does not generate a large amount of waste water, but also has a small degree of corrosion to the reaction vessel and low requirements for the treatment equipment, and does not require a series of cumbersome steps such as concentration and multiple purification, which is convenient for industrial expansion of production. Most of the organic non-metallic catalysts used have been commercialized, cheap and easy to obtain. At the same time, these catalysts are stable in nature, have no strict requirements on the temperature and humidity of the storage environment, and can also be recycled many times, which helps to further reduce costs.

[0045] The low molecular weight composition obtained by the regeneration treatment method can be directly used as a reaction raw material to prepare polymer materials or composite materials, etc., thereby realizing the recycling of plastic waste. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0047] Figure 1 The sample product in Example 1 of the present invention after being washed with chloroform and before being washed 1 HNMR spectrum.

[0048] Figure 2 These are optical photographs of the residues of the polylactic acid film disc of Test A1 of the present invention at 8 hours (8h), 16 hours (16h), 24 hours (24h), 32 hours (32h), 48 hours (48h) and 72 hours (72h) after the start of the reaction.

[0049] Figure 3The graph shows the change in conversion rate (average value) of the reaction system over time in some embodiments of the present invention; wherein, in tests A1 to A5, a polylactic acid film disc is placed in a pH = 1 aqueous solution containing 3.5 wt % diphenyl phosphate (DPP) (test A1), deionized water (test A2), a dry environment (3.5 wt % diphenyl phosphate DPP is mixed in the film) (test A3), a pH = 1 hydrochloric acid solution (test A4) and a pH = 13 NaOH aqueous solution (test A5).

[0050] Figure 4 is the peak molecular weight (M) of the reaction system in some embodiments of the present invention peak ) changes with time; wherein, the reaction system of Test A6 is polylactic acid pellets (pre-crushed to a diameter of <1 mm), diphenyl phosphate DPP (the mass ratio of DPP to polylactic acid pellets is 5%), the reaction temperature is 160°C oil bath, 2 drops of deionized water are added every 5 minutes, and the reaction is carried out for 0.5 hours; the difference between Test A7 and Test A6 is that no diphenyl phosphate DPP is added.

[0051] Figure 5 The degradation test was conducted with different polymer materials as substrates; A in the figure is a photo of the mixed plastic (polyethylene terephthalate PET + polypropylene PP + polyethylene PE + polylactic acid PLA) as the substrate before the reaction; B and C in the figure are photos of the degradation product (B in the figure) and the undegraded plastic (C in the figure) obtained after the mixed plastic was reacted as the substrate; D, E and F in the figure are the DSC curves of polyethylene terephthalate PET, polypropylene PP and polyethylene PE in the reaction substrate (mixed plastic) before and after treatment, respectively. m Is the melting point. DETAILED DESCRIPTION

[0052] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] The words "implementation mode" and "example" used herein are not necessarily to be interpreted as any embodiment described as "exemplary" to be superior or better than other embodiments. Unless otherwise specified, the performance index tests in the examples of this application are conducted using conventional test methods in the art. It should be understood that the terms described in this application are only for describing specific implementation modes and are not intended to limit the contents disclosed in this application.

[0054] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.

[0055] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0056] "Alkyl" refers to the part of a hydrocarbon with single bonds between carbon and hydrogen atoms removed. Phrases containing this term, such as "C 1 ~C 6 "Alkyl" refers to an alkyl group containing 1 to 6 carbon atoms, each occurrence of which can be independently C 1 Alkyl, C 2 Alkyl, C 3 Alkyl, C 4 Alkyl, C 5 Alkyl or C 6 Alkyl. Suitable examples include, but are not limited to, ethyl (Et, -CH 2 CH 3 ), 1-propyl (n-Pr, n-propyl, -CH 2 CH 2 CH 3 ), 1-methylethyl (i-Pr, i-propyl, -CH(CH 3 ) 2 ), 1-butyl (n-Bu, n-butyl, -CH 2 CH 2 CH 2 CH 3 ), 1-methylpropyl(s-Bu, s-butyl, -CH(CH 3 )CH 2 CH 3 ), 2-methylpropyl (i-Bu, i-butyl, -CH 2 CH(CH 3 ) 2 )、1,1-dimethylethyl(t-Bu、t-butyl、-C(CH 3 ) 3 ), 1-pentyl (n-pentyl, -CH 2 CH 2 CH 2 CH 2 CH 3 ), 1-methylbutyl (-CH(CH 3 )CH 2 CH 2 CH 3), 1-ethylpropyl (-CH(CH 2 CH 3 ) 2 )、1,1-dimethylpropyl(-C(CH 3 ) 2 CH 2 CH 3 )、1,2-dimethylpropyl(-CH(CH 3 )CH(CH 3 ) 2 ), 3-methylbutyl (-CH 2 CH 2 CH(CH 3 ) 2 ), 2-methylbutyl (-CH 2 CH(CH 3 )CH 2 CH 3 )、2,2-dimethylpropyl(-CH 2 C(CH 3 ) 3 )、1-hexyl (-CH 2 CH 2 CH 2 CH 2 CH 2 CH 3 ), 1-methylpentyl (-CH(CH 3 )CH 2 CH 2 CH 2 CH 3 ), 1-ethylbutyl (-CH(CH 2 CH 3 )CH 2 CH 2 CH 3 )、1,1-dimethylbutyl(-C(CH 3 ) 2 CH 2 CH 2 CH 3 ), 1,2-dimethylbutyl (-CH(CH 3 )CH(CH 3 )CH 2 CH 3 )、1,3-dimethylbutyl(-CH(CH 3 )CH 2 CH(CH 3 ) 2 ), 1-methyl-1-ethylpropyl (-C(CH 3 )(CH 2 CH 3 ) 2), 2-methyl-1-ethylpropyl (-CH(CH 2 CH 3 )CH(CH 3 ) 2 )、1,1,2-trimethylpropyl(-C(CH 3 ) 2 CH(CH 3 ) 2 )、1,2,2-trimethylpropyl(-CH(CH 3 )C(CH 3 ) 3 , 2-methylpentyl (-CH 2 CH(CH 3 )CH 2 CH 2 CH 3 ), 4-methylpentyl (-CH 2 CH 2 CH 2 CH(CH 3 ) 2 ), 3-methylpentyl (-CH 2 CH 2 CH(CH 3 )CH 2 CH 3 ), 2-ethylbutyl (-CH 2 CH(CH 2 CH 3 ) 2 )、2,3-dimethylbutyl(-CH 2 CH(CH 3 )CH(CH 3 ) 2 )、3,3-dimethylbutyl (-CH 2 CH 2 C(CH 3 ) 3 )、2,2-dimethylbutyl (-CH 2 C(CH 3 ) 2 CH 2 CH 3 ).

[0057] "Alkoxy" refers to a group having an -O-alkyl group, i.e., an alkyl group as defined above attached to the main chain structure via an oxygen atom. Phrases containing this term, such as "C 1 ~C 4 "Alkoxy" means an alkyl group containing 1 to 4 carbon atoms, each occurrence of which can be independently C 1 Alkoxy, C 2 Alkoxy, C 3 Alkoxy or C4 Suitable examples include, but are not limited to, methoxy (—O—CH 3 or -OMe), ethoxy (-O-CH 2 CH 3 or -OEt) and tert-butyloxy (-OC(CH 3 ) 3 or -Ot-Bu).

[0058] "Halogen" or "halo" refers to -F, -Cl, -Br or -I.

[0059] "Phenyl" refers to -C 6 H 5 The alkyl-substituted phenyl group includes at least one position of the phenyl group being substituted by an alkyl group.

[0060] The terms "and / or", "or / and", and "and / or" used in this article have a selection scope that includes any one of two or more related listed items, and also includes any and all combinations of the related listed items, said any and all combinations including any two related listed items, any more related listed items, or a combination of all related listed items.

[0061] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical range disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for broadly including quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.

[0062] The terms "substantially" and "approximately" used herein are used to describe the allowable small fluctuations in numerical values. It should be understood that as long as the numerical range is within the allowed fluctuation range, it is within the semantic scope of "substantially" or "approximately". For example, "substantially" and "approximately" cover the situation of no fluctuation. For example, they can refer to less than or equal to ±5%, such as less than or equal to ±2%, such as less than or equal to ±1%, such as less than or equal to ±0.5%, such as less than or equal to ±0.2%, such as less than or equal to ±0.1%, such as less than or equal to ±0.05%. The numerical data expressed or presented in the range format herein are used only for convenience and brevity, and should therefore be flexibly interpreted as including not only the values ​​explicitly listed as the limits of the range, but also all independent values ​​or sub-ranges contained in the range. For example, the numerical range of "1% to 5%" should be interpreted as including not only the explicitly listed values ​​of 1% to 5%, but also the independent values ​​and sub-ranges within the range shown. Thus, included in this numerical range are individual values ​​such as 2%, 3.5% and 4%, and sub-ranges such as 1% to 3%, 2% to 4% and 3% to 5%, etc. This principle also applies to ranges that list only one numerical value. Furthermore, such an interpretation applies regardless of the breadth of the range or the characteristics described.

[0063] Herein, "preferred", "better", "more preferred", and "suitable" are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of this application. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.

[0064] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0065] In this application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions of the listed features.

[0066] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0067] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.

[0068] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.

[0069] The mainstream alternatives to traditional petroleum-based plastics on the market are biodegradable polyester and polycarbonate materials represented by polylactic acid. Although these biodegradable materials can be degraded under certain conditions, they usually require professional industrial composting conditions, and the materials currently in use far exceed the processing capacity of existing industrial composting plants. In addition, even under industrial composting conditions, the material degradation cycle is usually 3 to 6 months, and the materials and degradation products are directly discharged into the natural environment, making it impossible to recycle and reuse resources.

[0070] Commonly used biodegradable polymer materials such as polylactic acid, polycaprolactone, polybutylene succinate, polybutylene adipate / terephthalate, etc., degrade very slowly under natural conditions and will not undergo significant changes in morphology even if left in the air for a year. Effective degradation of biodegradable polymer materials requires human intervention.

[0071] In order to better realize the treatment and recycling of degradable polymer materials, chemical recovery can be selected, and methods such as thermal cracking, alcoholysis and hydrolysis can be generally selected. The thermal cracking method has high reaction temperature, low yield of target product, more side reactions and easy racemization of product, and it is difficult to obtain high-purity products. Alcoholysis method is usually to treat waste materials with low alkyl alcohol or ethylene glycol under the action of catalyst to recycle hydroxy acids or esters therein, for example, patent documents (US5264614A, US5264617A) report alcoholysis recovery of polyhydroxyalkanoic acid ester (PHA) with low alkyl alcohol such as n-butanol as solvent, but it is necessary to add a large amount of strong acid catalyst (such as sulfuric acid), which is easy to corrode equipment, and the process is complicated, and it is difficult to expand to industrial scale, and neutralization and washing will also produce a large amount of waste water. There are other technical documents that use ionic liquids (CN102659590A), liquid Lewis acids (CN105017013A), CaO / MCF mesoporous alkaline molecular sieves (CN107382718A), alkaline low eutectic solvents (CN108837847A) and immobilized ionic liquids (CN110003009A) as catalysts to convert polylactic acid into corresponding lactic acid esters in solvents such as methanol. This has improved the problems of equipment corrosion, wastewater discharge and the inability to reuse catalysts to a certain extent, but these catalysts have not yet been commercialized, need to be prepared by themselves, have cumbersome steps, and do not have industrial transformation capabilities in the short term. The hydrolysis rule has the problem of slow hydrolysis speed, and it is difficult to recycle valuable products within a limited time. It usually requires high temperature and high pressure conditions and the catalysis of strong acids or strong bases, and the single processing volume is small, which cannot meet actual needs. In general, the degradation rate of degradable polymer materials in traditional chemical recycling methods is slow, the conversion rate of polymer substrates is low, and the complex reaction system makes it difficult to separate the products after the reaction, resulting in low yields and easy environmental pollution.

[0072] Therefore, there is an urgent need to develop a recycling method for degradable polymer materials with fast reaction speed, high conversion rate, high yield and green environmental protection, so as to be able to convert degradable polyester / polycarbonate materials into products with high added value, realize the recycling of degradable polyester / polycarbonate materials, and promote the green development of the industry.

[0073] The first aspect of the present application provides a method for regenerating a degradable polymer material, which uses an organic non-metallic catalyst with a specific structure to regenerate and recover the degradable polymer material. The specific organic non-metallic catalyst used has been screened through a large number of experiments and it has been found that the catalyst can efficiently catalyze the hydrolysis of degradable polymer materials such as polyester and polycarbonate.

[0074] In some embodiments, the organic non-metal catalyst having a specific structure can be selected from cyclic phosphate diesters and organic base compounds. Further, the structure of the cyclic phosphate diester compound also has Acidic sites (-OH) and Lewis basic sites (P=O), thereby playing a role in promoting degradation, non-limiting examples may include diphenyl phosphate-based organic non-metallic catalysts and binaphthol phosphate-based organic non-metallic catalysts.

[0075] In some embodiments, a method for regenerating a degradable polymer material is provided, comprising the following steps: degrading the degradable polymer material in a system in which an organic non-metallic catalyst and an aqueous solvent exist to obtain a degradation product;

[0076] in,

[0077] The degradable polymer material includes one or more of polyester material and polycarbonate material;

[0078] The organic non-metal catalyst is selected from one or more of diphenyl phosphate, binaphthol phosphate and organic bases. Further, the organic base is selected from one or more of nitrogen-containing heterobicyclic bases, 4-dimethylaminopyridine and phosphazene base compounds.

[0079] In some embodiments, the cyclic phosphodiester is an aromatic phosphodiester, which means having Ar 1 -O-(HO)P(=O)-O-Ar 2 ( ) structure, in which Ar 1 and Ar 2 Each of them is independently an aromatic group, further, the number of ring atoms of the aromatic ring can be 12 to 60, further, the number of ring atoms of the aromatic ring can be 12 to 56, and can also be selected from the interval consisting of any one or any two of the following ring atoms: 12, 16, 18, 20, 22, 24, 26, 28, 30, 32, 34, 36, 38, 40, 42, 44, 46, 48, 50, 52, 54, 56, 58 and 60. Ar1 and Ar2 can each independently be a monovalent group (see the structure shown in formula (I)), Ar 1 and Ar 2 It can also be connected by a covalent single bond, so that Ar 1 ,Ar 2 and -O(HO)P(=O)-O-, the covalent single bond forms a ring, for example, when Ar 1 and Ar 2 When both contain naphthalene rings, Ar 1 and Ar 2A binaphthyl structure can be formed, and a specific example can be found in formula (II). In some embodiments, Ar 1 ,Ar 2 and -O(HO)P(=O)-O- through Ar 1 and Ar 2 The covalent single bond between them forms a seven-membered ring structure. Further, Ar 1 and Ar 2 are each independently unsubstituted naphthyl or substituted naphthyl, in which case Ar 1 and Ar 2 A binaphthyl structure is formed therebetween. Furthermore, the oxy groups on both sides of -O-(HO)P(=O)- are respectively connected to a ring-forming carbon atom of a naphthalene ring, as shown in formula (II).

[0080] In this application, the organic non-metallic catalyst of diphenyl phosphate type refers to a catalyst having The two benzene rings can be independently unsubstituted or substituted, and further, the two benzene rings can be independently substituted by 0, one or more Q 1 Replace, any Q 1 may be independently selected from the group consisting of: halogen, -NO 2 , C 1 ~C 4 Alkoxy, C 1 ~C 6 Alkyl, halogen substituted C 1 ~C 6 Alkyl, phenyl and one or more Q a Substituted phenyl, any one of Q a There may be multiple substituents independently selected from the group consisting of halogen and C 1 ~C 4 alkyl.

[0081] In this application, the organic non-metallic catalyst of the binaphthol phosphate class refers to a catalyst having The two naphthalene rings can be independently unsubstituted or substituted, and further, the two naphthalene rings can be independently substituted by 0, one or more Q 2 Replace, any Q 2 may be independently selected from the following substituents: triphenylsilyl (-SiPh 3 , wherein Ph represents a phenyl group), a phenyl group and a substituted phenyl group, and further, the phenyl ring in the substituted phenyl group may be substituted by one or more substituents selected from the group consisting of halogen, -NO 2 , C 1 ~C 6 Alkyl, halogen substituted C 1 ~C 6Alkyl, phenyl, and one or more Q b Substituted phenyl, any one of Q b The substitution may be independently selected from the group consisting of halogen, -NO 2 , phenyl and C 1 ~C 4 alkyl.

[0082] In some embodiments, in the regeneration method, the diphenyl phosphate has a structure shown in formula (I):

[0083]

[0084] In formula (I), R 11 , R 12 , R 13 , R 14 , R 15 , R 21 , R 22 , R 23 , R 24 and R 25 are each independently selected from -H, halogen, -NO 2 , C 1 ~C 4 Alkoxy, C 1 ~C 6 Alkyl, halogen substituted C 1 ~C 6 any one of an alkyl group, a phenyl group, and a substituted phenyl group, wherein the phenyl ring in the substituted phenyl group is substituted by one or more substituents selected from the group consisting of halogen and C 1 ~C 4 alkyl.

[0085] In some embodiments, in the regeneration method, the binaphthol phosphate has a structure shown in formula (II):

[0086]

[0087] In formula (II), R 3 and R 3 ' can be independently selected from -H, -SiPh 3 or Wherein, “*” indicates the attachment site of a covalent single bond;

[0088] R 41 , R 42 , R 43 , R 44 and R 45 are each independently selected from -H, halogen, -NO 2 , C 1 ~C 6Alkyl, halogen substituted C 1 ~C 6 any one of an alkyl group, a phenyl group, and a substituted phenyl group, wherein the phenyl ring in the substituted phenyl group is substituted by one or more substituents selected from the group consisting of halogen, -NO 2 , phenyl and C 1 ~C 4 Alkyl; or R 41 , R 42 , R 43 , R 44 and R 45 At least two of them form a ring and participate in forming a fused ring, R 41 , R 42 , R 43 , R 44 and R 45 The ring-forming groups are each independently selected from -H, halogen, -NO 2 , C 1 ~C 6 Alkyl, halogen substituted C 1 ~C 6 any one of an alkyl group, a phenyl group, and a substituted phenyl group, wherein the phenyl ring in the substituted phenyl group is substituted by one or more substituents selected from the group consisting of halogen, -NO 2 , phenyl and C 1 ~C 4 alkyl.

[0089] In some embodiments, R in the structure of formula (I) 11 , R 12 , R 13 , R 14 , R 15 , R 21 , R 22 , R 23 , R 24 and R 25 Each independently selected from -H, -F, -Cl, -Br, -I, -NO 2 .

[0090] In some embodiments, R in the structure of formula (I) 11 , R 12 , R 13 , R 14 , R 15 , R 21 , R 22 , R 23 , R 24 and R 25 Each independently selected from C 1 ~C 4 Alkoxy; further can be independently selected from -OCH3 、-OCH 2 CH 3 、-OCH 2 CH 2 CH 3 、-OCH(CH 3 ) 2 、-OCH 2 CH 2 CH 2 CH 3 、-OCH 2 CH(CH 3 ) 2 、-OCH(CH 3 )CH 2 CH 3 、-OC(CH 3 ) 3 .

[0091] In some embodiments, R in the structure of formula (I) 11 , R 12 , R 13 , R 14 , R 15 , R 21 , R 22 , R 23 , R 24 and R 25 Each independently selected from C 1 ~C 6 Alkyl, i.e. C 1 Alkyl, C 2 Alkyl, C 3 Alkyl, C 4 Alkyl, C 5 Alkyl or C 6 Alkyl; further can be independently selected from: ethyl (Et, -CH 2 CH 3 ), 1-propyl (n-Pr, n-propyl, -CH 2 CH 2 CH 3 ), 1-methylethyl (i-Pr, i-propyl, -CH(CH 3 ) 2 ), 1-butyl (n-Bu, n-butyl, -CH 2 CH 2 CH 2 CH 3 ), 1-methylpropyl(s-Bu, s-butyl, -CH(CH 3 )CH 2 CH 3 ), 2-methylpropyl (i-Bu, i-butyl, -CH2 CH(CH 3 ) 2 )、1,1-dimethylethyl(t-Bu、t-butyl、-C(CH 3 ) 3 ), 1-pentyl (n-pentyl, -CH 2 CH 2 CH 2 CH 2 CH 3 ), 1-methylbutyl (-CH(CH 3 )CH 2 CH 2 CH 3 ), 1-ethylpropyl (-CH(CH 2 CH 3 ) 2 )、1,1-dimethylpropyl(-C(CH 3 ) 2 CH 2 CH 3 )、1,2-dimethylpropyl(-CH(CH 3 )CH(CH 3 ) 2 ), 3-methylbutyl (-CH 2 CH 2 CH(CH 3 ) 2 ), 2-methylbutyl (-CH 2 CH(CH 3 )CH 2 CH 3 ), 2,2-dimethylpropyl (-CH 2 C(CH 3 ) 3 )、1-hexyl (-CH 2 CH 2 CH 2 CH 2 CH 2 CH 3 ), 1-methylpentyl (-CH(CH 3 )CH 2 CH 2 CH 2 CH 3 ), 1-ethylbutyl (-CH(CH 2 CH 3 )CH 2 CH 2 CH 3 )、1,1-dimethylbutyl(-C(CH 3 ) 2 CH 2 CH2 CH 3 ), 1,2-dimethylbutyl (-CH(CH 3 )CH(CH 3 )CH 2 CH 3 )、1,3-dimethylbutyl(-CH(CH 3 )CH 2 CH(CH 3 ) 2 ), 1-methyl-1-ethylpropyl (-C(CH 3 )(CH 2 CH 3 ) 2 ), 2-methyl-1-ethylpropyl (-CH(CH 2 CH 3 )CH(CH 3 ) 2 )、1,1,2-trimethylpropyl(-C(CH 3 ) 2 CH(CH 3 ) 2 )、1,2,2-trimethylpropyl(-CH(CH 3 )C(CH 3 ) 3 , 2-methylpentyl (-CH 2 CH(CH 3 )CH 2 CH 2 CH 3 ), 4-methylpentyl (-CH 2 CH 2 CH 2 CH(CH 3 ) 2 ), 3-methylpentyl (-CH 2 CH 2 CH(CH 3 )CH 2 CH 3 ), 2-ethylbutyl (-CH 2 CH(CH 2 CH 3 ) 2 )、2,3-dimethylbutyl(-CH 2 CH(CH 3 )CH(CH 3 ) 2 )、3,3-dimethylbutyl (-CH 2 CH 2 C(CH 3 ) 3 ) and 2,2-dimethylbutyl (-CH2 C(CH 3 ) 2 CH 2 CH 3 ), and halogen-substituted C 1 ~C 6 Alkyl; Halogen substituted C 1 ~C 6 Alkyl, such as -CF 3 , -CF 2 CF 3 ,-C(CF 3 ) 3 wait.

[0092] In some embodiments, R in the structure of formula (I) 11 , R 12 , R 13 , R 14 , R 15 , R 21 , R 22 , R 23 , R 24 and R 25 Each independently selected from any one of phenyl and substituted phenyl, wherein the phenyl ring in the substituted phenyl is substituted by one or more substituents selected from the group consisting of halogen and C 1 ~C 4 alkyl.

[0093] In some embodiments, R in the structure of formula (I) 12 , R 13 , R 14 , R 15 , R 22 , R 23 , R 24 and R 25 For H.

[0094] In some embodiments, R in the structure of formula (I) 11 and R 21 are selected from the same group.

[0095] In some embodiments, the diphenyl phosphate has a structure shown in formula (I-1):

[0096]

[0097] In some embodiments, R in the structure of formula (I) 11 , R 13 , R 14 , R 15 , R 21 , R 23 , R 24 and R25 For H.

[0098] In some embodiments, R in the structure of formula (I) 12 and R 22 are selected from the same group.

[0099] In some embodiments, the diphenyl phosphate has a structure shown in formula (I-2):

[0100]

[0101] In some embodiments, R in the structure of formula (I) 11 , R 12 , R 14 , R 15 , R 21 , R 22 , R 24 and R 25 For H.

[0102] In some embodiments, R in the structure of formula (I) 13 and R 23 are selected from the same group.

[0103] In some embodiments, the diphenyl phosphate has a structure shown in formula (I-3):

[0104]

[0105] In some embodiments, R in the structure of formula (I) 12 , R 13 , R 14 , R 22 , R 23 and R 24 For H.

[0106] In some embodiments, R in the structure of formula (I) 11 , R 15 , R 21 and R 25 are selected from the same group.

[0107] In some embodiments, the diphenyl phosphate has a structure shown in formula (I-4):

[0108]

[0109] In some embodiments, R in the structure of formula (I) 12 , R 14 , R 22 and R 24 For H.

[0110] In some embodiments, R in the structure of formula (I) 11 , R 13 , R 15 , R 21 , R 23 and R 25 are selected from the same group.

[0111] In some embodiments, the diphenyl phosphate has a structure shown in formula (I-5):

[0112]

[0113] In some embodiments, R in the structure of formula (II) 3 and R 3 'Each independently selected from -H, -SiPh 3 ( )or “*” represents the attachment site.

[0114] In some embodiments, R in the structure of formula (II) 41 , R 42 , R 43 , R 44 and R 45 Each independently selected from -H, -F, -Cl, -Br, -I, -NO 2 .

[0115] In some embodiments, R in the structure of formula (II) 41 , R 42 , R 43 , R 44 and R 45 Each independently selected from C 1 ~C 6 Alkyl, i.e. C 1 Alkyl, C 2 Alkyl, C 3 Alkyl, C 4 Alkyl, C 5 Alkyl or C 6 Alkyl; further can be independently selected from: ethyl (Et, -CH 2 CH 3 ), 1-propyl (n-Pr, n-propyl, -CH 2 CH 2 CH 3 ), 1-methylethyl (i-Pr, i-propyl, -CH(CH 3 ) 2 ), 1-butyl (n-Bu, n-butyl, -CH 2 CH 2 CH 2 CH3 ), 1-methylpropyl(s-Bu, s-butyl, -CH(CH 3 )CH 2 CH 3 ), 2-methylpropyl (i-Bu, i-butyl, -CH 2 CH(CH 3 ) 2 )、1,1-dimethylethyl(t-Bu、t-butyl、-C(CH 3 ) 3 ), 1-pentyl (n-pentyl, -CH 2 CH 2 CH 2 CH 2 CH 3 ), 1-methylbutyl (-CH(CH 3 )CH 2 CH 2 CH 3 ), 1-ethylpropyl (-CH(CH 2 CH 3 ) 2 )、1,1-dimethylpropyl(-C(CH 3 ) 2 CH 2 CH 3 )、1,2-dimethylpropyl(-CH(CH 3 )CH(CH 3 ) 2 ), 3-methylbutyl (-CH 2 CH 2 CH(CH 3 ) 2 ), 2-methylbutyl (-CH 2 CH(CH 3 )CH 2 CH 3 )、2,2-dimethylpropyl(-CH 2 C(CH 3 ) 3 )、1-hexyl (-CH 2 CH 2 CH 2 CH 2 CH 2 CH 3 ), 1-methylpentyl (-CH(CH 3 )CH 2 CH 2 CH 2 CH 3 ), 1-ethylbutyl (-CH(CH 2 CH 3 )CH2 CH 2 CH 3 )、1,1-dimethylbutyl(-C(CH 3 ) 2 CH 2 CH 2 CH 3 ), 1,2-dimethylbutyl (-CH(CH 3 )CH(CH 3 )CH 2 CH 3 )、1,3-dimethylbutyl(-CH(CH 3 )CH 2 CH(CH 3 ) 2 ), 1-methyl-1-ethylpropyl (-C(CH 3 )(CH 2 CH 3 ) 2 ), 2-methyl-1-ethylpropyl (-CH(CH 2 CH 3 )CH(CH 3 ) 2 )、1,1,2-trimethylpropyl(-C(CH 3 ) 2 CH(CH 3 ) 2 )、1,2,2-trimethylpropyl(-CH(CH 3 )C(CH 3 ) 3 , 2-methylpentyl (-CH 2 CH(CH 3 )CH 2 CH 2 CH 3 ), 4-methylpentyl (-CH 2 CH 2 CH 2 CH(CH 3 ) 2 ), 3-methylpentyl (-CH 2 CH 2 CH(CH 3 )CH 2 CH 3 ), 2-ethylbutyl (-CH 2 CH(CH 2 CH 3 ) 2 )、2,3-dimethylbutyl(-CH 2 CH(CH 3 )CH(CH 3 )2 )、3,3-dimethylbutyl (-CH 2 CH 2 C(CH 3 ) 3 ) and 2,2-dimethylbutyl (-CH 2 C(CH 3 ) 2 CH 2 CH 3 ), and halogen-substituted C 1 ~C 6 Alkyl; Halogen substituted C 1 ~C 6 Alkyl, such as -CF 3 , -CF 2 CF 3 ,-C(CF 3 ) 3 wait.

[0116] In some embodiments, R in the structure of formula (II) 41 , R 42 , R 43 , R 44 and R 45 Each independently selected from any one of phenyl and substituted phenyl, wherein the phenyl ring in the substituted phenyl is substituted by one or more substituents selected from the group consisting of halogen, -NO 2 , phenyl and C 1 ~C 4 Alkyl-substituted phenyl; for example 4-ClC 6 H 4 、4-NO 2 C 6 H 4 、4-CH 3 C 6 H 4 , 4-CF 3 C 6 H 4 、4-t-BuC 6 H 4 、4-PhC 6 H 4 、4-(2,4,6-(CH 3 ) 3 C 6 H 2 )C 6 H 4 、3,5-(CF 3 ) 2 C 6 H 3 、3,5-t-Bu 2 C 6 H3 、3,5-Ph 2 C 6 H 3 、2,4,6-CH 3 C 6 H 2 、2,4,6-(i-Pr) 3 C 6 H 2 The alkyl-substituted phenyl group includes an alkyl group that replaces at least one position of the phenyl group, for example, R 42 and R 44 are selected from phenyl groups substituted with multiple methyl groups, such as 2,4,6-(CH 3 ) 3 C 6 H 2 When R 3 and R 3 ' can be independently selected from -5'-2,2",4,4",6,6"-hexamethyl-1,1':3",1"-terphenyl ( ).

[0117] In some embodiments, R in the structure of formula (II) 41 , R 42 , R 43 , R 44 and R 45 Two or more substituents in form a fused ring; further, R 41 , R 42 , R 43 , R 44 and R 45 The fused ring formed is 1-naphthyl ( )、2-naphthyl( )、4-β-naphthyl-phenyl( )、9-Anthracene ( )、9-Fiki( ).

[0118] In some embodiments, the structural formula shown in formula (II) can also be in its R configuration ( ) or S configuration ( ).

[0119] In some embodiments, the organic base is selected from 1,8-diazabicyclo[5.4.0]undec-7-ene ( )、1,5,7-triazidobicyclo[4.4.0]dec-5-ene( )、7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene( ), 4-dimethylaminopyridine and one or more phosphazene base compounds.

[0120] In some embodiments, in the regeneration method, the organic base is selected from one or more of nitrogen-containing heterobicyclic bases, 4-dimethylaminopyridine and phosphazene base compounds.

[0121] In some embodiments, the nitrogen-containing heterobicyclic base is selected from the group consisting of:

[0122]

[0123] Formula (III), Y is -CH 2- , -NH- or -N(CH 3 )-; n is 1 or 2.

[0124] In some embodiments, the phosphazene base compound has a structure shown in formula (IV):

[0125] (i.e. )

[0126] (IV)

[0127] In formula (IV), R is halogen, C 1 ~C 4 Alkyl or C 1 ~C 4 Alkoxy. Phosphazene base compounds refer to monomers or polymers thereof, such as tert-butylimino-tri(dimethylamino)phosphorane ( )、1-tert-butyl-2,2,4,4,4-penta(dimethylamino)-2Λ5,4Λ5-di(phosphorus nitrogen compound) ), cyclotriphosphazene base (such as ) and 1-tert-butyl-4,4,4-tris(dimethylamino)-2,2-bis[tris(dimethylamino)-phosphoranylideneamino]-2Λ5,4Λ5-linked di(phosphorus nitrogen compound) ( ).

[0128] In some embodiments, the diphenyl phosphate catalyst is selected from one or more of diphenyl phosphate, bis(4-nitrophenyl)phosphate and bis(2,6-dimethylphenyl)phosphate.

[0129] In some embodiments, the binaphthol phosphate catalyst is one or more of binaphthol phosphate, R-binaphthol phosphate, R-3,3'-bis(triphenylsilyl)binaphthol phosphonate and R-3,3'-bis(2,4,6-triisopropylphenyl)binaphthol phosphonate.

[0130] In some embodiments, the organic base catalyst is selected from 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,5,7-triazidobicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 4-dimethylaminopyridine, tert-butylimino-tris(dimethylamino)phosphorane, 1-tert-butyl-2,2,4,4,4-penta(dimethylamino)-2Λ5,4Λ5-bis(phosphorus nitrogen-based compound) and cyclotriphosphazene base and 1-tert-butyl-4,4,4-tris(dimethylamino)-2,2-bis[tris(dimethylamino)-phosphoranylideneamino]-2Λ5,4Λ5-bis(phosphorus nitrogen-based compound) One or more.

[0131] In some embodiments, in the regeneration method, the diphenyl phosphate is selected from diphenyl phosphate (DPP), bis(4-nitrophenyl)phosphate (BNPP), bis(2,6-xylyl)phosphate (DXP), and the binaphthol phosphate is selected from binaphthol phosphate (1,1'-binaphthyl-2,2'-diylhydrogenphosphate, BNDHP), R-binaphthol phosphate ((R)-(-)-1,1'-binaphthyl-2,2'-diylhydrogenphosphate, R-BNDHP), R-3,3'-bis(triphenylsilyl)binaphtholphosphonate ((R)-(-)-3,3'-bis(triphenylsilyl)-1,1'-binaphthyl-2,2'-diylhydrogenphosphate, R-BNDHP), R-3,3'-bis(triphenylsilyl)binaphtholphosphonate ((R)-(-)-3,3'-bis(triphenylsilyl)-1,1'-binaphthyl-2,2'-diyl hydrogenphosphate, referred to as R-TiPSY), R-3,3'-bis(2,4,6-triisopropylphenyl)binapthylphosphonate ((R)-3,3'-Bis(2,4,6-trisopropylphenyl)-1,1'-binapthyl-2,2'-diyl The invention relates to a method for preparing an organic base comprising: preparing an organic base comprising: a first organic base and a second organic base; a second ...

[0132] In some embodiments, the organic non-metal catalyst can be selected from diphenyl phosphate, binaphthol phosphate and organic bases. For example, diphenyl phosphate (DPP), bis(4-nitrophenyl)phosphate (BNPP), di(2,6-xylyl)phosphate (DXP), binaphthol phosphate (1,1'-binaphthyl-2,2'-diyl hydrogenphosphate, BNDHP), R-binaphthol phosphate ((R)-(-)-1,1'-binaphthyl-2,2'-diylhydrogenphosphate, R-BNDHP), R-3,3'-bis(triphenylsilyl)binaphthol phosphonate ((R)-(-)-3,3'-bis(triphenylsilyl)-1,1'-binaphthyl-2,2'-diyl hydrogenphosphate, referred to as R-TiPSY), R-3,3'-bis(2,4,6-triisopropylphenyl)binapthylphosphonate ((R)-3,3'-Bis(2,4,6-trisopropylphenyl)-1,1'-binapthyl-2,2'-diyl The invention further comprises one or more of 1,4-dimethylaminopyridine (DMAP), 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD), 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (MTBD), 4-dimethylaminopyridine (DMAP) and cyclic trimeric phosphazene base (CTPB). Most of the organic non-metallic catalysts selected above are mature commercial products, which are not only cheap and easy to obtain, but also can catalyze the efficient hydrolysis of degradable polymer materials to obtain degradation products with low degree of polymerization (for example, close to monomers, or oligomers with a degree of polymerization below 10). The low molecular weight degradation products obtained by the method provided in the present application can be reused as raw materials, for example, can be used in the preparation of polymers, and realize efficient closed-loop recycling of degradable polymer waste.

[0133] In the above-mentioned regeneration treatment method of degradable polymer materials, the conversion rate of degradable polymer materials is high, the polymerization degree of degradation products is low (for example, close to the monomer level), and the low molecular weight composition in the system after the degradation reaction can achieve a high proportion (for example, more than 95%). In addition, the treatment method has low equipment requirements, simple post-treatment operation, green process and low cost.

[0134] Understandably, the regeneration treatment method can efficiently degrade the degradable polymer material into monomers and / or oligomers. It is also possible to control the degree of degradation within a certain range by adjusting the reaction raw materials, process parameters (such as the content of water in the reaction system, the content of the catalyst, the reaction time, the reaction temperature and the reaction pressure, etc.), i.e., obtain degradation products with a certain molecular weight and distribution and / or a certain conversion rate. The degradation products with a certain molecular weight and distribution and / or a certain conversion rate can be directly or conveniently used as the raw material of the polymerization reaction under the condition of not carrying out the treatment such as purification, or under the condition of simple separation treatment, to prepare the degradable polymer material through polymerization and other reactions.

[0135] In the regeneration method of the first aspect of the present invention, after the degradation treatment, the degradable polymer material is degraded into products with reduced molecular weight.

[0136] In some embodiments, the degradation products are substantially low molecular weight products. In the present invention, unless otherwise specified, low molecular weight products mainly refer to degradation products with a molecular weight of ≤1500 Da.

[0137] Unless otherwise specified, the terms "oligomer" and "oligomer" in this application have the same meaning and can be used interchangeably.

[0138] In some embodiments, degradation products may include monomers and / or oligomers at near monomer levels.

[0139] Unless otherwise specified, the oligomer or oligomer in this application mainly refers to a polymer with a molecular weight of ≤1500Da and containing fewer repeating units.

[0140] Some molecules in the degradation products may be water-soluble when the molecular weight is low (e.g., PLA oligomer molecular weight ≤500 Da, corresponding to degree of polymerization ≤6.9). Therefore, the water-soluble molecules in the degradation products are recorded as "water-soluble small molecules".

[0141] Unless otherwise specified, the "near monomer level oligomer" in this application mainly refers to an oligomer with a degree of polymerization ≤ 10, which may also be recorded as a "quasi-monomer oligomer" or a "quasi-monomer oligomer".

[0142] Taking polylactic acid (PLA) in polyester materials as an example, polylactic acid can be continuously degraded under the conditions of organic non-metallic catalyst and water to form low molecular weight degradation products basically composed of monomers and / or oligomers (such as monomers and / or oligomers close to the monomer level). The low molecular weight degradation products can be directly used as raw materials for efficient polymerization reaction, and can be used to prepare polymerization products with a certain molecular weight (such as number average molecular weight ≥ 50kDa). It is also possible to control the degree of polymerization of the degradation products in the reaction system to a certain level (such as ≤ 8) by appropriately adjusting the raw material ratio, process parameters, etc., and then the degradation products in the degradation product system are first used to prepare lactide, and then a high molecular weight polymerization product (such as number average molecular weight ≥ 150kDa) is prepared using lactide as a raw material.

[0143] In some embodiments, in the regeneration method, the number average molecular weight of the degradable polymer material is 10kDa to 250kDa, and can further be 10kDa to 150kDa, and further can be 10kDa to 130kDa, and can also be selected from any one of the following number average molecular weight values ​​or an interval consisting of any two number average molecular weight values: 10kDa, 20kDa, 30kDa, 40kDa, 50kDa, 60kDa, 70kDa, 80kDa, 90kDa, 100kDa, 110kDa, 120kDa, 130kDa, 140kDa, 150kDa, 160kDa, 170kDa, 180kDa, 190kDa, 200kDa, 210kDa, 220kDa, 230kDa, 240kDa, 250kDa, etc.

[0144] In some embodiments, in the regeneration method, the weight average molecular weight of the degradable polymer material is 10kDa to 500kDa, further 10kDa to 250kDa, further 30kDa to 230kDa, and can also be selected from any one of the following weight average molecular weight values ​​or an interval consisting of any two weight average molecular weight values: 10kDa, 20kDa, 30kDa, 40kDa, 50kDa, 60kDa, 70kDa, 80kDa, 90kDa, 100kDa, 110kDa, 120kDa, 130kDa, 140kDa, 150kDa, 160kDa, 170kDa , 180kDa, 190kDa, 200kDa, 210kDa, 220kDa, 230kDa, 240kDa, 250kDa, 260kDa, 270kDa, 280kDa, 290kDa, 300kDa, 310kDa, 320kDa, 330kDa, 340 kDa, 350kDa, 360kDa, 370kDa, 380kDa, 390kDa, 400kDa, 410kDa, 420kDa, 430kDa, 440kDa, 450kDa, 460kDa, 470kDa, 480kDa, 490kDa, 500kDa, etc.

[0145] In some embodiments, in the regeneration method, the mass ratio of water in the system to the degradable polymer material is (0.01-10):1, further can be (0.1-1):1, further can be (0.08-0.33):1:, and can also be selected from any one of the following mass ratios or an interval consisting of any two mass ratios: (0.01:1), (0.02:1), (0.03:1), (0.04:1), (0.05:1), (0.06:1), (0.07:1), (0.08:1), (0.083:1), (0.1:1), (0.15:1), (0.156:1) (0.2:1), (0.25:1), (0.3:1), (0.31:1) , (0.32:1), (0.33:1), (0.34:1), (0.35:1), (0.36:1), (0.37:1), (0.38:1), (0.39:1), (0.4:1), (0.5:1), (0.6:1), (0.7:1), (0.8:1), (0.9:1), (1:1), (1.3:1), (1.5:1), (2:1), (2.5:1), (3:1), (3.5:1), (4:1), (4.5:1), (5:1), (5.5:1), (6:1), (6.5:1), (7:1), (7.5:1), (8:1), (8.5:1), (9:1), (9.5:1), (10:1). A more appropriate water amount relative to the mass ratio of the degradable polymer material is more conducive to improving the degradation rate of the degradable polymer material. If the water amount in the system is higher than the mass ratio of the degradable polymer material, the internal temperature of the system is difficult to exceed the boiling point of the solvent (taking water as an example, 100°C) under normal pressure, which slows down the reaction process, and the water as a raw material will boil violently and evaporate in large quantities, which poses certain operational risks; if the water amount in the system is lower than the mass ratio of the degradable polymer material, it may cause insufficient amount of raw materials to participate in the reaction, reduce the probability of contact between reactants, and slow down the reaction rate, which may lead to a higher degree of polymerization of the final product.

[0146] In some embodiments, in the regeneration method, the mass ratio of the organic non-metallic catalyst to the degradable polymer material is (0.001-0.1):1, further can be (0.01-0.05:1), further can be (0.035-0.05:1), and can also be selected from any one of the following mass ratios or any two mass ratios: (0.001:1), (0.002:1), (0.003:1), (0.004:1), (0.005:1), (0.006:1), (0.007:1), (0.008:1), (0.0088:1) , (0.009:1), (0.01:1), (0.015:1), (0.02:1), (0.025:1), (0.03:1), (0.031:1), (0.032:1), (0.033:1), (0.034:1), (0.035:1), (0.036:1), (0.037:1), (0.038:1), (0.039:1), (0.04:1), (0.045:1), (0.05:1), (0.06:1), (0.07:1), (0.08:1), (0.09:1), (0.1:1), etc. A more appropriate catalyst amount relative to the mass ratio of the degradable polymer material is more conducive to reducing the economic cost of the recycling scheme. If the mass ratio of the catalyst to the degradable polymer material is too high, the use of a large amount of catalyst increases the raw material cost of the regeneration process; if the mass ratio of the catalyst to the degradable polymer material is too low, it may cause the degradation rate to be too slow, increasing time cost and energy consumption.

[0147] The degradation treatment of degradable polymer materials can be carried out under the condition of small amount of catalyst, with high catalytic efficiency and low cost.

[0148] In some embodiments, in the regeneration method, the average degree of polymerization of the degradation product is ≤20, further ≤15, further ≤10, and can also be selected from any one of the following average degree of polymerization values ​​or an interval consisting of any two average degree of polymerization values: 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, etc. The average degree of polymerization of the degradation product can also be selected from any one of the following ranges, such as 1-20, 1-15, 1-10, 2-20, 2-15, 2-12, 2-10, 2.3-9.6, etc.

[0149] Average degree of polymerization ( )Analysis method: Number average molecular weight (M n )÷repeating unit molecular weight. n=121kDa) raw material as an example, the molecular weight of its repeating unit is 72Da, and the average degree of polymerization is calculated by deducting the molecular weight of the end group 18Da from the number average molecular weight.

[0150]

[0151] In some embodiments, in the regeneration treatment method, the molar percentage of the monomer in the degradation product is ≥30%, further ≥50%, further ≥80%, and can also be selected from the following molar percentage values ​​of any one monomer or the interval composed of the molar percentage values ​​of any two monomers: 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 80%, 90%, etc. The molar percentage of the monomer in the degradation product can also be selected from any of the following ranges, such as 30% to 60%, 30% to 70%, 30% to 80%, 30% to 90%, 30% to 100%, etc. It can be understood that the above-mentioned regeneration treatment method is used to degrade the degradable polymer material, and as the degradation treatment time is extended, the molar percentage of the monomer in the degradation product can be higher. In this application, unless otherwise specified, the molar percentage of the monomer in the degradation product refers to: the percentage of the molar number of the monomer to the total molar number of the degradation product.

[0152] Taking the degradation product of polylactic acid as an example, it was dissolved in DMSO-d 6 The Fourier transform nuclear magnetic resonance spectrometer was used to characterize 1 HNMR spectrum, the molar percentage of lactic acid was calculated by the following formula:

[0153]

[0154] Among them, I 1.23 The methyl group (HOOCCH(CH 3 )OH) characteristic peak integral value, I 1.27 The 1.27 ppm corresponds to the terminal methyl group (-COCH(CH 3 It is understood that when different batches of tests are performed, the chemical shifts of the characteristic peaks 1.23ppm and 1.27ppm may shift. However, those skilled in the art can determine the measured chemical shifts according to the characteristic peak attribution method. 1 The characteristic peaks in the H NMR spectrum correspond to 1.23 ppm and 1.27 ppm.

[0155] In some embodiments, in the regeneration method, among the degradation products, the mass proportion of low molecular weight products relative to the degradation products is ≥80%, further can be ≥90%, and further can be ≥95%.

[0156] In this application, unless otherwise specified, the mass percentage of low molecular weight products in the system refers to: the weight percentage of low molecular weight products in the degradation products. In this application, the standard for considering that all products in the reaction system are low molecular weight products is that the degradation products are detected by gel permeation chromatography (GPC) and Fourier transform nuclear magnetic resonance (NMR) spectrometers, and no polymer characteristic peaks appear. Taking the degradation products of PLA as an example, the elution peak in the GPC spectrum is overall shifted backward, and the peak signal corresponding to the molecules with a molecular weight of more than 1500Da is basically not observed. 1 In the H NMR spectrum, the signals of the characteristic peaks of methyl groups (1.5-1.6 ppm) and methine groups (5.3-5.5 ppm) corresponding to the polymer were hardly observed.

[0157] In some embodiments, in the regeneration method, among the degradation products, the mass percentage of the low molecular weight products relative to the total mass of the degradation products is ≥80%, further ≥90%, and further ≥95%.

[0158] In some embodiments, in the regeneration method, the water-soluble small molecule conversion rate is ≥20%, and can further be ≥23%, and can also be selected from any of the following water-soluble small molecule conversion rate values ​​or any two water-soluble small molecule conversion rate values: 20%, 23.7%, 25%, 30%, 32.6%, 35%, 40%, 45%, 50%, 53%, 55%, 60%, 61.6%, 65%, 70%, 72.1%, 74.1%, 75%, 80%, 85%, 86%, 88.3%, 90%, 90.4%, 91%, 92.8%, 95%, 99.2%, etc. It can be understood that when the degradable polymer material is degraded by the above-mentioned regeneration method, the value of the water-soluble small molecule conversion rate in the degradation product can be higher as the degradation treatment time is prolonged.

[0159] In this application, unless otherwise specified, the conversion rate of polymer raw materials into water-soluble small molecules (hereinafter referred to as "water-soluble small molecule conversion rate") refers to the ratio of the amount of the initial raw material that has been degraded and dissolved in water after the degradation reaction to the initial raw material when the system continues to react to the preset termination or termination conditions. Specifically, the mass ratio can be used as a standard for calculation and judgment. In terms of numerical values, the "conversion rate of water-soluble small molecules" can be calculated based on the mass percentage of water-soluble products (corresponding to water-soluble small molecules) in the degradation products relative to the degraded raw materials (i.e., polymer raw materials).

[0160] Calculation method for the conversion rate of water-soluble small molecules: The degradation product was placed in deionized water and stirred at room temperature for 0.5 h to dissolve. After centrifugation, the insoluble precipitate was collected, freeze-dried and weighed. The conversion rate (mass ratio) of the polymer to the water-soluble small molecules was calculated by the following formula:

[0161]

[0162] Among them, m input is the mass of the polymer before the reaction, m residue is the mass of the insoluble matter remaining after the reaction.

[0163] In some embodiments, in the regeneration method, the polydispersity index (PDI) of the degradable polymer material is ≤3.3, further can be 1 to 3.3, and further can be 1 to 3.27.

[0164] In this application, unless otherwise specified, the polydispersity index (PDI) is used to describe the molecular weight distribution of polymers. The calculation method of the polydispersity index (PDI) is as follows: w Divide by M n The larger the value, the wider the molecular weight distribution. Numerically, PDI can also be equal to molar mass dispersity (denoted as ).

[0165] In some embodiments, the degradable polymer material is selected from polylactic acid (PLA), polyglycolic acid (PGA), polyε-caprolactone (PCL), polylactic acid-glycolic acid copolymer (PLGA), polyglycolic acid-ε-caprolactone copolymer (PCGA), polylactic acid-ε-caprolactone copolymer (PCLA), polyδ-valerolactone (PVL), polybutyrolactone (PBL), polybutylene succinate (PBS), polybutylene adipate / terephthalate (PBET), polybutylene terephthalate (PBET), polybutylene succinate (PBS), polybutylene terephthalate (PBET ... One or more of poly(terephthalate), referred to as PBAT), poly(hydroxyalkanoates), referred to as PHA, and poly(trimethylenecarbonate), referred to as PTMC.

[0166] In some embodiments, the regeneration method includes the following steps: in the system where the organic non-metallic catalyst and the aqueous solvent exist, subjecting the first degradable polymer material to a first degradation treatment to obtain a first degradation product; mixing the i-th degradation product and the i+1-th degradable polymer material, subjecting the i+1-th degradation treatment to obtain the i+1-th degradation product, wherein i is an integer ≥1, and the i+1-th degradable polymer material includes at least the second degradable polymer material; and ending the degradation treatment when i+1=n to obtain the n-th degradation product, wherein n is an integer ≥2, and the average degree of polymerization of the n-th degradation product is ≤10.

[0167] In the present application, degradable polymer material and water are continuously added to the degradation product, the content of the catalyst in the reaction system is reduced, and a secondary degradation reaction is carried out, and oligomers and / or monomers corresponding to the degradable polymer material can still be obtained, that is, the regeneration treatment of the degradable polymer material can be carried out continuously, which is conducive to industrial continuous production.

[0168] Taking n=2 as an example, the regeneration method comprises the following steps:

[0169] (1) subjecting a first degradable polymer material to a first degradation treatment in a system in which the organic non-metallic catalyst and the aqueous solvent exist to obtain a first degradation product;

[0170] (2) mixing the first degradation product and the second degradable polymer material, and performing a second degradation treatment to obtain a second degradation product. The average degree of polymerization of the second degradation product can refer to the above definition, for example, ≤20, and further for example, ≤10.

[0171] Taking n=4 as an example, in the system where the organic non-metallic catalyst and the aqueous solvent exist, the first degradable polymer material is subjected to a first degradation treatment to obtain a first degradation product;

[0172] mixing the first degradation product and the second degradable polymer material, performing a second degradation treatment, and obtaining a second degradation product;

[0173] mixing the second degradation product and the third degradable polymer material, performing a third degradation treatment, and obtaining a third degradation product;

[0174] The third degradation product and the fourth degradable polymer material are mixed and subjected to a fourth degradation treatment to obtain a fourth degradation product; the average degree of polymerization of the fourth degradation product can refer to the above definition, for example ≤20, further for example ≤10, etc.

[0175] Taking n=10 as an example, the regeneration method comprises the following steps:

[0176] In the system where the organic non-metallic catalyst and the aqueous solvent exist, subjecting the first degradable polymer material to a first degradation treatment to obtain a first degradation product;

[0177] mixing the first degradation product and the second degradable polymer material, performing a second degradation treatment, and obtaining a second degradation product;

[0178] Repeat the step of "subjecting the degradation product and the added new degradable polymer material to degradation treatment" 8 times, terminate the degradation treatment, and obtain the 10th degradation product. The average degree of polymerization of the 10th degradation product can refer to the above definition, for example ≤20, further for example ≤10, etc.

[0179] In some embodiments, in the regeneration method, the temperature of any degradation treatment is independently 25°C to 200°C, further 50°C to 200°C, and further 125°C to 200°C.

[0180] In some embodiments, in the regeneration treatment method, the temperature of any degradation treatment is independently 125°C to 200°C, further 130°C to 200°C, further 140°C to 180°C, and can also be selected from any one of the following temperatures or any two of the following temperatures: 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, etc. A more suitable reaction temperature is conducive to improving the degradation efficiency of the degradable polymer material. If the reaction temperature is too high, it may cause the water in the system to evaporate violently, which on the one hand loses the reaction raw materials, and on the other hand makes the operation dangerous, and puts forward higher requirements on the reaction equipment; if the reaction temperature is too low, it may cause a slow reaction speed, and the degradation of the degradable polymer material into oligomers and / or monomers takes a long time, increasing time cost and energy consumption.

[0181] In the present application, the temperature of the degradation treatment can be the actual temperature of the reaction system, or can be the ambient temperature of the reaction system, such as the water bath temperature, oil bath temperature, etc.

[0182] In some embodiments, in the regeneration method, the time of any degradation treatment is independently 0.25h to 5h, further 1h to 4h, further 1.5h to 4h, and can also be selected from any one of the following time or any two time intervals: 0.25h, 0.5h, 0.75h, 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3h, 3.2h, 3.4h, 3.6h, 3.8h, 4h. A more appropriate reaction time is conducive to obtaining the target product more efficiently. If the reaction time is too long, it may increase the time cost and energy consumption; if the reaction time is too short, the degradation product may not meet the requirements of recycling.

[0183] In some embodiments, in the regeneration method, the temperature of any degradation treatment is independently 125° C. to 200° C., and the time of any degradation treatment is independently 0.25 h to 5 h.

[0184] In some embodiments, in the regeneration method, the temperature of any degradation treatment is independently 130° C. to 200° C., and the time of any degradation treatment is independently 1 h to 4 h.

[0185] In some embodiments, in the regeneration method, the temperature of any degradation treatment is independently 140° C. to 180° C., and the time of any degradation treatment is independently 1.5 h to 4 h.

[0186] In some embodiments, in the regeneration treatment method, the pressure of any degradation treatment is independently 100 ± 5 kPa. It can also be selected from any one of the following pressures or an interval consisting of any two pressures: 95 kPa, 96 kPa, 97 kPa, 98 kPa, 100 kPa, 101 kPa, 102 kPa, 103 kPa, 104 kPa, 105 kPa, etc. The regeneration process can be carried out in a non-sealed environment and non-high temperature and high pressure conditions, the efficiency of catalytic degradation is high, and the degradable polymer material can be quickly converted into reusable oligomers and / or monomer raw materials. By adjusting the reaction pressure, the boiling point of the solvent can be affected and the internal temperature of the system can be affected. In addition, it can also affect the intensity of molecular motion, which will affect the reaction rate. If the reaction pressure is high, the internal temperature of the system rises and the molecular collision is more intense, the reaction becomes faster, but higher requirements are placed on the equipment; if the reaction pressure is low, it may cause the internal temperature of the system to be low and the probability of molecular collision is reduced, and the probability of reaction is reduced, so that the reaction slows down.

[0187] The degradation treatment of degradable polymer materials can be carried out under conditions without strong acids, strong bases and organic solvents, which helps to improve the problems of equipment corrosion and wastewater discharge in industrial applications.

[0188] In some embodiments, the regeneration method further comprises the following steps:

[0189] The degradation product is washed with an organic solvent, wherein the organic solvent is selected from one or more of chloroform, petroleum ether, carbon disulfide, ether, dichloromethane, benzene, toluene and ethyl acetate. It can be understood that the process of washing the degradation product with an organic solvent is also called extraction treatment.

[0190] The degradation products after degradation treatment can be effectively separated from the organic non-metallic catalyst by simple washing (such as extraction). The separated degradation products can be directly used as raw materials for the polymerization process without concentration or re-purification, which is convenient for industrial production.

[0191] In some embodiments, the regeneration method comprises the following steps: adding a degradable polymer material, an organic non-metallic catalyst and water into a reaction vessel, and carrying out a degradation reaction at 125°C to 200°C under a dispersion condition (such as under a stirring condition) (optionally, the degradation time can be as defined above, for example, 0.25h to 5h); further, the mass ratio of the organic non-metallic catalyst: water: degradable polymer material can be (0.001 to 0.1): (0.08 to 10): 1. In the regeneration method, the degradation reaction can be carried out in an atmospheric environment of 100±5kP.

[0192] In some embodiments, the regeneration treatment method comprises the following steps: adding a degradable polymer material, an organic non-metallic catalyst and water into a reaction vessel, carrying out a degradation reaction at 125°C to 200°C under a dispersion condition (such as under a stirring condition) (optionally, the degradation time can be as defined above, for example, 0.25h to 5h), and washing with an organic solvent after cooling; further, the mass ratio of the organic non-metallic catalyst: water: degradable polymer material can be (0.001 to 0.1): (0.08 to 10): 1; further, the organic solvent can be any one of chloroform, petroleum ether, and dichloromethane or any combination thereof, and further, the organic solvent can be any one of chloroform, petroleum ether, and dichloromethane. In the regeneration treatment method, the degradation reaction can be carried out in an atmospheric environment of 100±5kP.

[0193] In some embodiments, the regeneration treatment method comprises the following steps: adding a degradable polymer material, an organic non-metallic catalyst and water into a reaction vessel, carrying out a degradation reaction at 160±20°C under dispersed conditions (such as under stirring conditions) (optionally, the degradation time can be as defined above, for example, 1.5±1h), and washing with an organic solvent after cooling; further, the mass ratio of the organic non-metallic catalyst: water: degradable polymer material can be (0.035±0.02): (0.3±0.1): 1; further, the organic solvent can be any one of chloroform, petroleum ether, and dichloromethane. In the regeneration treatment method, the degradation reaction can be carried out in an atmospheric environment of 100±5kP.

[0194] In some embodiments, the regeneration treatment method comprises the following steps: adding a degradable polymer material, an organic non-metallic catalyst and water into a reaction vessel, carrying out a degradation reaction at 160±10°C under dispersed conditions (such as under stirring conditions) (optionally, the degradation time can be as defined above, for example, 1.5±0.5h), and washing with an organic solvent after cooling; further, the mass ratio of the organic non-metallic catalyst: water: degradable polymer material can be (0.035±0.005): (0.3±0.05): 1; further, the organic solvent can be any one of chloroform, petroleum ether, and dichloromethane. In the regeneration treatment method, the degradation reaction can be carried out in an atmospheric environment of 100±5kP.

[0195] In some embodiments, the regeneration treatment method comprises the following steps: adding a degradable polymer material, an organic non-metallic catalyst and water into a reaction vessel, carrying out a degradation reaction at 160±10°C under a dispersed condition (such as under a stirring condition) (optionally, the degradation time can be as defined above, for example, 1.5±0.5h), and washing with an organic solvent after cooling; further, the mass ratio of the organic non-metallic catalyst: water: degradable polymer material can be (0.0035±0.001): (0.15±0.05): 1; further, the organic solvent can be any one of chloroform, petroleum ether, and dichloromethane. In the regeneration treatment method, the degradation reaction can be carried out in an atmospheric environment of 100±5kP.

[0196] The second aspect of the present application provides a low molecular weight composition, wherein the low molecular weight composition is a degradation product of a degradable polymer material, and the low molecular weight composition can be prepared according to the regeneration method described in the first aspect.

[0197] In some embodiments, the low molecular weight composition is the low molecular weight product of the first aspect.

[0198] In some embodiments, the average degree of polymerization of the low molecular weight composition is ≤20, further ≤15, and further ≤10. The average degree of polymerization of the low molecular weight composition can also be selected from any one of the following average degree of polymerization values ​​or an interval consisting of any two average degree of polymerization values: 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, etc. The average degree of polymerization of the degradation product can also be selected from any one of the following ranges, such as 1-20, 1-15, 1-10, 2-20, 2-15, 2-12, 2-10, etc.

[0199] The low molecular weight composition can be obtained by hydrolyzing a degradable polymer material (abandoned degradable polymer material can be used) with a catalyst. The product purification method is simple, the process is economical, and has a good cost advantage.

[0200] The third aspect of the present application provides a method for recycling degradable polymer materials.

[0201] In some embodiments, the recycling method comprises the following steps: performing a polymerization reaction using a low molecular weight composition as an initial raw material; wherein the low molecular weight composition is a degradation product prepared by the regeneration method described in the first aspect or the low molecular weight composition described in the second aspect.

[0202] By using a low molecular weight composition obtained by degrading a degradable polymer material (abandoned degradable polymer material may be used) as a raw material, a polymerization reaction can be carried out under the catalysis of a traditional catalyst to obtain the polymer material again, thereby realizing the secondary use of the degraded polymer material, that is, recycling. This recycling method is not only cost-effective but also environmentally friendly.

[0203] In some embodiments, the method for recycling degradable polymer materials comprises the following steps: S100: degrading the degradable polymer materials in a system in which an organic non-metallic catalyst and an aqueous solvent exist, and obtaining a degradation product system containing degradation products after the reaction is completed;

[0204] S200: directly using the degradation product system as a raw material for a synthesis reaction.

[0205] Step S100 may refer to the first aspect of the present invention.

[0206] The synthesis reaction in step S200 is not particularly limited as long as the degradation product in step S100 participates in the reaction.

[0207] In some embodiments, in step S200, the degradation product system is directly used as a raw material for synthesizing lactide. At this time, the molecular weight or degree of polymerization of the degradation products in the degradation product system can refer to the above. For example, the average degree of polymerization of the degradation products in the degradation product system is ≤8, and further the average degree of polymerization can be ≤5, etc. For another example, the weight ratio or molar ratio of the monomer-like oligomers in the degradation products can be increased, for example, the weight ratio or molar ratio of the monomer-like oligomers in the degradation products is controlled to be greater than or equal to a certain value, such as ≥50%, ≥80%, ≥90%, etc.

[0208] In some embodiments, in step S200, the degradation product system is directly used as a raw material in a polymerization reaction, and can be used to prepare a homopolymer or a copolymer.

[0209] The organic non-metal catalyst used in the present application can be separated from the degradation product by a simple separation step. In addition, according to the requirements of the subsequent polymerization reaction or other treatment methods, the degradation product may not be separated from the organic non-metal catalyst, and the reaction system obtained by the degradation treatment may be directly used for the next step. For example, the degradation of polylactic acid PLA is catalyzed by the organic non-metal catalyst diphenyl phosphate DPP. If the degradation product system obtained by the degradation treatment is used to prepare lactide monomer, since the preparation process of lactide is usually subjected to a reduced pressure distillation operation, the degradation product in the degradation product system can be separated from the organic non-metal catalyst diphenyl phosphate DPP while preparing lactide. At this time, there is no need to perform additional separation operations on the degradation product system in advance; the catalyst for synthesizing lactide can be directly added to the system. In the reaction process of catalyzing the aforementioned degradation product to prepare lactide, the generated lactide can enter the container for receiving the lactide product or enter the next step of the reaction process, so as to achieve separation from the components of the degradation product system and the catalyst for synthesizing lactide.

[0210] In a fourth aspect of the present application, there is provided an application of an organic non-metallic catalyst in the degradation treatment of a degradable polymer material;

[0211] Wherein, the organic non-metallic catalyst and the degradable polymer material are as defined in the first aspect of the present application.

[0212] By using organic non-metallic catalysts, polyester / polycarbonate materials (such as discarded polyester / polycarbonate materials) can be converted into products with high added value under mild conditions. The obtained products can be simply removed from the impurities to obtain oligomers and / or monomers corresponding to the degradable polyester / polycarbonate materials, which can be used again in the polymerization process, thus realizing the recycling of plastics. The obtained monomer aqueous solution is of comparable quality to commercially available products and can be used for conventional purposes after extraction to remove the catalyst.

[0213] It can be understood that the technical solution in this application can be used to degrade polyester / polycarbonate materials (such as discarded polyester / polycarbonate materials) into low molecular weight degradation products (such as oligomers and / or monomers), and the degradation products can also be used for the next synthesis process or utilization. For example, using polylactic acid as a polymer material (raw material), the degradation product (such as lactic acid monomer aqueous solution) that has been degraded is subjected to conventional separation steps such as extraction and impurity removal to obtain lactic acid monomer. Lactic acid, as a widely used platform molecule, can be used in chemical, food, cosmetics, pharmaceutical and other industries in addition to preparing polylactic acid. Taking the chemical industry as an example, lactic acid can be used to prepare a variety of commodities and intermediate chemicals, such as lactic acid esters, 1,2-propylene glycol, acrylic acid, pyruvic acid, acetaldehyde, 2,3-pentanedione, etc. In addition, lactic acid can be used as an antifreeze agent, a fixing agent for wool fabric printing, and can also be used for softening leather, descaling, cleaning, adjusting pH, etc. It is also a green organic solvent. Some specific embodiments are provided below.

[0214] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.

[0215] For experimental methods in the following examples where specific conditions are not specified, reference is made to the instructions given in the present invention, and may also be made according to experimental manuals or conventional conditions in the art, or according to conditions recommended by manufacturers, or reference may be made to experimental methods known in the art.

[0216] Unless otherwise specified, the raw materials used in the following experiments can be purchased from the market.

[0217] The following examples are not particularly limited, and the performance test methods and evaluation criteria in this application are as follows:

[0218] Number average molecular weight (M n ), weight average molecular weight (M w ) and polydispersity index (PDI) test method: Gel permeation chromatography (1260, Agilent) was used to test the sample at a concentration of 10 mg / mL in tetrahydrofuran (THF) and tested at 35°C. The mobile phase was tetrahydrofuran with a flow rate of 1.0 mL / min. The standard sample was narrowly distributed polystyrene (PS). The lower limit of the gel permeation chromatography test was 550 Da-600 Da. According to the sample 1 The H NMR spectrum can be used to calculate the number average molecular weight (M) of the sample. n ), average degree of polymerization ( ) and the molar proportion of the monomers therein, the specific test method is as follows: lactic acid and / or its oligomers are dissolved in DMSO-d at a concentration of 100 mg / mL 6 The test was carried out at 25°C using a Fourier transform nuclear magnetic resonance spectrometer (400 MHz, AVANCEIII HD, Bruker). A small amount of D 2 O. Other compounds were dissolved in CDCl at a concentration of 10 mg / mL 3 Conduct a test.

[0219] Example 1

[0220] 2.5g of PLA (degradable polymer material), 0.0875g of DPP (organic non-metallic catalyst) and 0.75g of deionized water (equivalent to a system containing a water solvent) were added to a reaction tube, stirred with a magnetic stirrer, and reacted in an oil bath at 160°C (ambient temperature) for 1.5h under atmospheric pressure (equivalent to normal pressure), and washed with chloroform (organic solvent) after cooling. Calculation shows that the mass ratio of organic non-metallic catalyst: water: degradable polymer material is 0.035:0.3:1.

[0221] The polylactic acid model used in Example 1 is LX175 (TotalEnergies Corbion), the number average molecular weight (M) of the PLA used was measured by gel permeation chromatography n ), weight average molecular weight (M w ) and polydispersity index (PDI) were 121.0 kDa, 199.7 kDa and 1.65 respectively; the catalyst used was diphenyl phosphate DPP.

[0222] The molecular weight of the degradation product was lower than the detection limit of GPC, indicating that its molecular weight was lower than 600Da. The average molecular weight of the degradation product was 191Da and the average degree of polymerization ( ) was 2.4, of which 90.4% was converted into water-soluble small molecules. 1 H NMR spectrum Figure 1 As shown in the figure, the methyl peak shifts are different in different chemical environments. Among them, the methyl group (OHCOCH(CH 3 )OH) peak ( Figure 1 The position marked as a in the figure) and the position marked as 1.27 ppm are the methyl groups (-COCH(CH 3 )OH) peak ( Figure 1 The positions marked as c in the figure) and 1.38-1.50 ppm are other methyl groups in the lactic acid oligomers (-COCH(CH 3)O-)peak( Figure 1 The peak at 4.03-5.50 ppm is the peak corresponding to the methine in lactic acid monomer and its oligomer ( Figure 1 The positions marked as b, d, and e in the figure overlap with the water peak. The 7.0-7.4 ppm peak corresponds to the characteristic peak of the benzene ring of DPP ( Figure 1 The positions marked as i, h, and g in the figure are shown in Table 1). Except for the position at 2.5 ppm corresponding to the solvent DMSO-d 6 There is no other obvious signal except the characteristic peak. The calculation method of the molar percentage of monomers in the degradation product and the conversion rate of polymers into water-soluble small molecules is as described above. Taking Example 1 as an example, the specific calculation method is as follows: the characteristic peak integral value corresponding to the terminal methyl of lactic acid oligomer at 1.27ppm is set to 1, the characteristic peak integral value at 1.23ppm is 1.15, and the characteristic peak integral value at 1.38-1.50ppm is 3.01. It can be calculated that the number average molecular weight of the degradation product is (90+72*3.01 / (1+1.15)≈191), and the molar percentage of lactic acid monomers in the degradation product is 1.15 / (1+1.15)≈0.535; the remaining water-insoluble solid residue is 0.2406g, and the conversion rate of polymers into water-soluble small molecules is (1-0.2406 / 2.5≈0.904).

[0223] In the present application, unless otherwise specified, the degradation product obtained by regenerating the degradable polymer material (in the presence of an organic non-metallic catalyst and water) using a gel permeation chromatography is tested, and the measured molecular weight is lower than the GPC detection limit, which means that the molecular weight of the polymer material contained in the obtained degradation product is lower than 600Da.

[0224] Example 2

[0225] The raw materials and degradation process of Example 2 are basically the same as those of Example 1, except that the amount of the organic non-metallic catalyst used is 0.025 g, and the organic solvent used to wash the degradation product is petroleum ether. Calculation shows that the mass ratio of the organic non-metallic catalyst: water: degradable polymer material is 0.01:0.3:1.

[0226] The washed degradation product was tested in the same manner as in Example 1. Its molecular weight was lower than the GPC detection limit. The average molecular weight of the degradation product was calculated by hydrogen nuclear magnetic resonance spectrum to be 387 Da, the average degree of polymerization was 5.1, and the conversion rate was 40.0%.

[0227] Example 3

[0228] The raw materials and degradation process of Example 3 are basically the same as those of Example 1, except that the amount of the organic non-metallic catalyst used is 0.05 g, and the organic solvent used to wash the degradation product is dichloromethane. Calculation shows that the mass ratio of the organic non-metallic catalyst: water: degradable polymer material is 0.02:0.3:1.

[0229] The washed degradation product was tested in the same manner as in Example 1. Its molecular weight was lower than the GPC detection limit. The average molecular weight of the degradation product was calculated by hydrogen nuclear magnetic resonance spectrum to be 289 Da, the average degree of polymerization was 3.8, and the conversion rate was 61.6%.

[0230] Example 4

[0231] The raw materials and degradation process of Example 4 are basically the same as those of Example 1, except that the amount of the organic non-metallic catalyst used is 0.125 g, and the organic solvent used to wash the degradation product is ether. Calculation shows that the mass ratio of the organic non-metallic catalyst: water: degradable polymer material is 0.05:0.3:1.

[0232] The washed degradation product was tested in the same manner as in Example 1. Its molecular weight was lower than the GPC detection limit. The average molecular weight of the degradation product was calculated by hydrogen nuclear magnetic resonance spectrum to be 185 Da, the average degree of polymerization was 2.3, and the conversion rate was 99.2%.

[0233] Embodiments 5 to 9

[0234] The raw materials and degradation processes of Examples 5 to 9 are substantially the same as those of Example 1, except that the ambient temperatures of the degradation treatment are different, namely 120° C., 140° C., 150° C., 170° C. and 180° C.

[0235] The washed degradation products were tested in the same manner as in Example 1. The molecular weight of the degradation products was lower than the GPC detection limit. The conversion rate of the degradation products and the average molecular weight and average degree of polymerization calculated by the measured H NMR spectrum are shown in Table 1.

[0236] Table 1 Test results of degradation products after washing in Examples 5 to 9

[0237]

[0238] Embodiments 10 to 13

[0239] The raw materials and degradation processes of Examples 10 to 13 are substantially the same as those of Example 1, except that the degradation treatment time is different, namely 0.5 h, 1 h, 2 h and 2.5 h, respectively.

[0240] The washed degradation products were tested in the same manner as in Example 1. The molecular weight of the degradation products was lower than the detection limit of GPC. The conversion rate of the degradation products and the average molecular weight, average degree of polymerization and conversion rate calculated by the measured hydrogen nuclear magnetic resonance spectrum are shown in Table 2.

[0241] Table 2 Test results of the degradation products after washing in Examples 10 to 13

[0242]

[0243] Embodiment 14

[0244] 2.5 g of polylactic acid PLA (equivalent to the first degradable polymer material), 0.0875 g of diphenyl phosphate DPP, and 0.75 g of deionized water were added to a reaction tube, stirred with a magnetic stirrer and ventilated with air, and reacted in an oil bath at 160° C. for 1.5 h (equivalent to the first degradation treatment). The average molecular weight of the obtained product (equivalent to the first degradation product) was calculated based on the measured nuclear magnetic resonance hydrogen spectrum to be 191 Da ( ), 2.5 g of PLA (equivalent to the second degradable polymer material) and 0.35 g of deionized water were added again, and the reaction was continued for 1.5 h (equivalent to the second degradation treatment). The average molecular weight of the degradation product (equivalent to the second degradation product) was calculated based on the measured nuclear magnetic resonance hydrogen spectrum to be 181 Da ( ), the PLA raw material was added repeatedly for 8 degradation steps (equivalent to the 3rd to 10th degradation treatments), and the average molecular weight of the final degradation product (equivalent to the 10th degradation product) was calculated based on the measured nuclear magnetic resonance hydrogen spectrum to be 193Da ( ); wherein, a total of 25 g of PLA was added (equivalent to the sum of the masses of the 1st to 10th degradable polymer materials), and water was also added in the 3rd to 10th degradation treatments, and the mass ratio of the added water to the degradable polymer material remained the same as that of the second time.

[0245] Embodiment 15

[0246] 1000 g of polylactic acid PLA (equivalent to the first degradable polymer material), 35 g of diphenyl phosphate DPP, and 83 g of deionized water were added to a normal pressure reactor, mechanically stirred, and reacted in an oil bath at 160°C for 1.5 h (equivalent to the first degradation treatment). The average molecular weight of the obtained degradation product (equivalent to the first degradation product) was calculated based on the measured nuclear magnetic resonance hydrogen spectrum to be 347 Da ( ), 1000 g of polylactic acid PLA (equivalent to the second degradable polymer material) and 83 g of deionized water were added again, and the reaction was continued for 1.5 h (equivalent to the second degradation treatment). The average molecular weight of the degradation product (equivalent to the second degradation product) was calculated based on the measured nuclear magnetic resonance hydrogen spectrum to be 284 Da ( ), repeated twice (equivalent to the third and fourth degradation treatments), the average molecular weight of the final product (equivalent to the fourth degradation product) was calculated based on the measured nuclear magnetic resonance hydrogen spectrum to be 287Da ( ); wherein, a total of 4000 g of PLA was added (equivalent to the sum of the masses of the 1st to 4th degradable polymer materials), and water was also added in the 3rd and 4th degradation treatments, and the mass ratio of the added water to the degradable polymer material remained the same as that of the 1st and 2nd times.

[0247] 100 g of the degradation product was placed in a two-necked bottle, 0.75 g of ZnO was added as a catalyst, the temperature was gradually raised from 180 °C to 230 °C, and the crude lactide product was obtained by vacuum distillation. After washing with water and purification by recrystallization with ethyl acetate, the crude lactide product was prepared in the presence of a conventional industrial catalyst Sn(Oct) 2 The PLA product (M n =390,600,M w =505,300), realizing the closed-loop recycling of PLA.

[0248] Example 16

[0249] The raw materials and degradation process of Example 16 are basically the same as those of Example 1, except that the catalyst used is bis(4-nitrophenyl) phosphate (BNPP for short).

[0250] The washed degradation product was tested in the same manner as in Example 1. Its molecular weight was lower than the GPC detection limit. The average molecular weight of the degradation product was calculated by hydrogen nuclear magnetic resonance spectrum to be 182 Da, the average degree of polymerization was 2.3, and the conversion rate was 84.6%.

[0251] Embodiment 17

[0252] The raw materials and degradation process of Example 17 are basically the same as those of Example 1, except that the catalyst used is binaphthol phosphate (BNDHP for short), and the degradation treatment time is 4 hours.

[0253] The washed degradation product was tested in the same manner as in Example 1. Its molecular weight was lower than the GPC detection limit. The average molecular weight of the degradation product was calculated by hydrogen nuclear magnetic resonance spectrum to be 243 Da, the average degree of polymerization was 3.1, and the conversion rate was 73.8%.

[0254] Embodiment 18

[0255] The raw materials and degradation process of Example 18 are basically the same as those of Example 1, except that the catalyst used is 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU for short), the degradation treatment time is 3 h, and the organic solvent used to wash the degradation product is petroleum ether.

[0256] The washed degradation product was tested in the same manner as in Example 1. Its molecular weight was lower than the GPC detection limit. The average molecular weight of the degradation product was calculated by hydrogen nuclear magnetic resonance spectrum to be 333 Da, the average degree of polymerization was 4.4, and the conversion rate was 68.0%.

[0257] Embodiment 19

[0258] The raw materials and degradation process of Example 19 are basically the same as those of Example 1, except that the catalyst used is 1,5,7-triazidobicyclo[4.4.0]dec-5-ene (TBD for short), and the degradation treatment time is 4 hours.

[0259] The washed degradation product was tested in the same manner as in Example 1. Its molecular weight was lower than the GPC detection limit. The average molecular weight of the degradation product was calculated by hydrogen nuclear magnetic resonance spectrum to be 249 Da, the average degree of polymerization was 3.2, and the conversion rate was 73.0%.

[0260] Embodiment 20

[0261] The raw materials and degradation process of Example 20 are basically the same as those of Example 1, except that the degradable polymer material used is polycaprolactone (PCL for short), the degradation treatment time is 3 hours, and the organic solvent used to wash the degradation product is dichloromethane.

[0262] Polycaprolactone model 6800 (Perstorp Company), the number average molecular weight (M n ), weight average molecular weight (M w ) and polydispersity index PDI were 65.2 kDa, 213.1 kDa and 3.27, respectively.

[0263] The washed degradation product was tested in the same manner as in Example 1, and the molecular weight thereof was lower than the lower limit of GPC detection.

[0264] Embodiment 21

[0265] The raw materials and degradation process of Example 21 are basically the same as those of Example 1, except that the degradable polymer material used is polylactic acid-glycolic acid copolymer (PLGA for short), and the degradation treatment time is 2.5 h.

[0266] Poly(lactic acid-co-glycolic acid) copolymer was prepared in the laboratory. The number average molecular weight (M) of PLGA was measured by gel permeation chromatography. n ), weight average molecular weight (M w ) and polydispersity index PDI were 9.97 kDa, 15.0 kDa and 1.50, respectively.

[0267] The washed degradation product was tested in the same manner as in Example 1, and the molecular weight thereof was lower than the lower limit of GPC detection.

[0268] Embodiment 22

[0269] The raw materials and degradation process of Example 22 are basically the same as those of Example 1, except that the degradable polymer material used is polybutylene adipate / terephthalate (PBAT for short), and the degradation treatment time is 2.5 h.

[0270] Polybutylene adipate / terephthalate model is F Blend C1200 (BASF SE), the number average molecular weight (M n ), weight average molecular weight (M w ) and polydispersity index (PDI) were 17.3 kDa, 31.0 kDa and 1.79, respectively.

[0271] The washed degradation product was tested in the same manner as in Example 1, and the molecular weight thereof was lower than the lower limit of GPC detection.

[0272] Embodiment 23

[0273] The raw materials and degradation process of Example 23 are basically the same as those of Example 1, except that the amount of the organic non-metallic catalyst used is 0.125 g, the degradable polymer material used is poly (3-hydroxybutyrate-co-4-hydroxybutyrate) (P34HB for short), the degradation treatment time is 3 hours, and the organic solvent used to wash the degradation product is dichloromethane. Calculation shows that the mass ratio of the organic non-metallic catalyst: water: degradable polymer material is 0.05:0.3:1.

[0274] The model of poly (3-hydroxybutyrate-co-4-hydroxybutyrate) is EM 10080 (ECOMRNN). The number average molecular weight (M) of P34HB used was measured by gel permeation chromatography. n ), weight average molecular weight (M w ) and polydispersity index PDI were 128.9 kDa, 228.6 kDa and 1.77 respectively, and the testing conditions were the same as in Example 1.

[0275] The washed degradation product was tested in the same manner as in Example 1, and the molecular weight thereof was lower than the lower limit of GPC detection.

[0276] Embodiment 24

[0277] The raw materials and degradation process of Example 24 are basically the same as those of Example 1, except that the amount of the organic non-metallic catalyst used is 0.125 g, the degradable polymer material used is polybutylene succinate (PBS for short), the degradation treatment time is 4 hours, and the organic solvent used to wash the degradation product is dichloromethane. Calculation shows that the mass ratio of the organic non-metallic catalyst: water: degradable polymer material is 0.05:0.3:1.

[0278] The model of polybutylene succinate was BioPBSTM FD72PM (Public Company Limited). The number average molecular weight (M) of the PBS used was measured by gel permeation chromatography. n ), weight average molecular weight (M w ) and polydispersity index (PDI) were 25.2 kDa, 43.2 kDa and 1.71, respectively.

[0279] The washed degradation product was tested in the same manner as in Example 1, and the molecular weight thereof was lower than the lower limit of GPC detection.

[0280] Embodiment 25

[0281] The raw materials and degradation process of Example 25 are basically the same as those of Example 1, except that the degradable polymer material used is a 3D printing material.

[0282] 3D printing materials were purchased from an online retail platform (Taobao.com), and the number average molecular weight (M n ), weight average molecular weight (M w ) and polydispersity index (PDI) were 10.9 kDa, 18.4 kDa and 1.69, respectively.

[0283] The washed degradation product was tested in the same manner as in Example 1. Its molecular weight was lower than the GPC detection limit. The average molecular weight was calculated by hydrogen nuclear magnetic resonance spectrum to be 193 Da, the average degree of polymerization was 2.4, and the conversion rate was 78.2%.

[0284] Embodiment 26

[0285] The raw materials and degradation process of Example 26 are basically the same as those of Example 1, except that the amount of the organic non-metallic catalyst used is 0.125 g, the degradable polymer material used is a plastic straw (mainly composed of polylactic acid and polybutylene succinate), the degradation treatment time is 4 hours, and the organic solvent used to wash the degradation product is dichloromethane. Calculation shows that the mass ratio of the organic non-metallic catalyst: water: degradable polymer material is 0.05:0.3:1.

[0286] Plastic straws were purchased from an online retail platform (Taobao.com), and the number average molecular weight (M n ), weight average molecular weight (M w ) and polydispersity index (PDI) coefficients were 122.3 kDa, 166.6 kDa and 1.36, respectively.

[0287] The washed degradation product was tested in the same manner as in Example 1, and the molecular weight thereof was lower than the lower limit of GPC detection.

[0288] Embodiment 27

[0289] The raw materials and degradation process of Example 27 are basically the same as those of Example 1, except that the degradable polymer material used is polytrimethylene carbonate (PTMC for short), the organic solvent used to wash the degradation product is dichloromethane, and the degradation treatment time is 3 hours.

[0290] Polytrimethylene carbonate was prepared in the laboratory, and the number average molecular weight (M) of the PTMC was measured by gel permeation chromatography. n ), weight average molecular weight (M w ) and polydispersity index (PDI) were 23.6 kDa, 36.0 kDa and 1.53, respectively.

[0291] The washed degradation product was tested in the same manner as in Example 1, and the molecular weight thereof was lower than the lower limit of GPC detection.

[0292] Embodiment 28

[0293] A regeneration method for degradable polyester / polycarbonate materials:

[0294] 2.5 g of polylactic acid PLA, 0.0875 g of diphenyl phosphate DPP, and 0.75 g of deionized water were added to a reaction tube, stirred with a magnetic stirrer, and reacted in an oil bath at 160°C for 1.5 h. 2.5 g of deionized water was then added, and the reaction was continued for 1.5 h. After cooling, the product was washed with chloroform. The molecular weight of the product was lower than the detection limit of GPC, and all of the product was converted into water-soluble small molecules. The average molecular weight of the degradation product was 108 ( ), of which 86.2 mol % is lactic acid monomer, which is similar to the commercially available 85% lactic acid aqueous solution (monomer proportion 86.0 mol %).

[0295] Embodiment 29

[0296] The raw materials and degradation process of Example 29 are basically the same as those of Example 1, except that the catalyst used is bis(4-nitrophenyl) phosphate (BNPP for short), and the degradation treatment time is 0.5 h.

[0297] The washed degradation product was tested in the same manner as in Example 1. Its molecular weight was lower than the GPC detection limit. The average molecular weight of the degradation product was calculated by hydrogen nuclear magnetic resonance spectrum to be 215 Da, the average degree of polymerization was 2.7, and the conversion rate was 62.4%.

[0298] Embodiment 30

[0299] The raw materials and degradation process of Example 30 are basically the same as those of Example 1, except that the catalyst used is bis(4-nitrophenyl) phosphate (BNPP for short), and the degradation treatment time is 1 hour.

[0300] The washed degradation product was tested in the same manner as in Example 1. Its molecular weight was lower than the GPC detection limit. The average molecular weight of the degradation product was calculated by hydrogen nuclear magnetic resonance spectrum to be 186 Da, the average degree of polymerization was 2.3, and the conversion rate was 85.8%.

[0301] Embodiment 31

[0302] The raw materials and degradation process of Example 31 are basically the same as those of Example 1, except that the catalyst used is binaphthol phosphate (BNDHP for short), and the degradation treatment time is 3.5 h.

[0303] The washed degradation product was tested in the same manner as in Example 1. Its molecular weight was lower than the GPC detection limit. The average molecular weight of the degradation product was calculated by hydrogen nuclear magnetic resonance spectrum to be 291 Da, the average degree of polymerization was 3.8, and the conversion rate was 74.3%.

[0304] Embodiment 32

[0305] The raw materials and degradation process of Example 32 are basically the same as those of Example 1, except that the catalyst used is R-binaphthol phosphate (R-BNDHP for short), and the degradation treatment time is 5 hours.

[0306] The washed degradation product was tested in the same manner as in Example 1. Its molecular weight was lower than the GPC detection limit. The average molecular weight of the degradation product was calculated by hydrogen nuclear magnetic resonance spectrum to be 247 Da, the average degree of polymerization was 3.2, and the conversion rate was 70.8%.

[0307] The inventors of the present application also conducted the following (i) to (v) groups of experiments:

[0308] (I) Polylactic acid (M) with a diameter of 8 mm n =121.0 kDa, M w =199.7kDa) film discs (17±1mg) were placed in 5 different reaction environments for 5 tests (respectively denoted as A1, A2, A3, A4 and A5), the ambient temperature was 70°C, and 3 parallel tests were performed for each test. The conversion rate of the system was calculated on the 1st day, 2nd day, 3rd day, 4th day and 5th day of each test, and the apparent morphology of the residual polymer in the system was observed regularly:

[0309] (1) Test A1: The aforementioned polylactic acid film disc was placed in a diphenyl phosphate (DPP) aqueous solution (3.5wt%, 10mL, pH=1). After one day of reaction, it was observed that the polylactic acid film disc had broken; after two days, it was difficult to observe obvious insoluble matter in the system, and the polylactic acid film disc was basically converted into a water-soluble small molecule product (the conversion rate was calculated to be >95%). Figure 2 Optical photographs of polylactic acid film residues of one of the three parallel experiments of Experiment A1 at 8 hours (8h), 16 hours (16h), 24 hours (24h), 32 hours (32h), 48 hours (48h) and 72 hours (72h) after the start of the reaction, where the dotted line indicates that there is no solid residue. The conversion rate of the system reached 95.3% after 2 days of reaction, and reached 100% after 3 days of reaction (the change in conversion rate can be seen in Figure 3 and Table 3).

[0310] (2) Test A2: The aforementioned polylactic acid film disc was placed in water. The conversion rate of this system was only 5.1% after 5 days of reaction (the change in conversion rate can be seen in Figure 3 and Table 3), the degradation rate of the polylactic acid film disc in this system is significantly lower than that in test A1. The reason may be that no organic non-metallic catalyst is added. Even if there is water in the system, the degradation process is very slow without the action of the catalyst.

[0311] (3) Test A3: The aforementioned polylactic acid film disc is placed in a dry environment, and 3.5 wt% diphenyl phosphate DPP is mixed in the polylactic acid film disc. The preparation method of the polylactic acid film disc mixed with 3.5 wt% DPP is as follows: DPP is added to a DCM solution containing PLA, and after the solvent evaporates, a sample film (M) containing diphenyl phosphate DPP evenly distributed is obtained. n =84.3 kDa, M w =136.8kDa), the film was placed in a sealed glass container with phosphorus pentoxide to remove as much moisture as possible from the environment. The conversion rate of the system was 11.9% after 5 days of reaction (the change in conversion rate can be seen in Figure 3 and Table 3), the degradation rate of the polylactic acid film disc in this system is significantly lower than that of test A1 but slightly higher than that of test A2. The reason may be that although no additional water is added, there is a certain amount of water vapor in the atmospheric environment. When a certain amount of diphenyl phosphate DPP is mixed in, the degradation process of the polylactic acid film disc can proceed, but the degradation rate is slower.

[0312] (4) Test A4: The aforementioned polylactic acid film disc was placed in a diluted hydrochloric acid aqueous solution (pH = 1). The conversion rate of the system was 10.4% after 5 days of reaction (the change in conversion rate can be seen in Figure 3 and Table 3).

[0313] (5) Test A5: The aforementioned polylactic acid film disc was placed in a sodium hydroxide aqueous solution (pH = 13). The conversion rate of the system was 65.7% after 5 days of reaction (the change in conversion rate can be seen in Figure 3 and Table 3).

[0314] Table 3 Conversion rate of polylactic acid film discs in the system from the first day to the fifth day in the three parallel tests of test A1 to test A5 into water-soluble small molecules

[0315]

[0316] From the comparison between Experiment A1 and Experiment A3, it can be seen that the degradation of PLA catalyzed by diphenyl phosphate is mainly carried out through hydrolysis. When the water content in the system is very small (only residual water in the raw materials and water in the environment), the degradation rate of PLA is greatly slowed down. When the water in the system is basically exhausted, PLA basically does not degrade. In aqueous solvents, diphenyl phosphate can significantly catalyze the hydrolysis of PLA.

[0317] From the comparison of Test A1, Test A4 and Test A5, it can be seen that the effect of diphenyl phosphate catalyzing the hydrolysis of PLA is much better than that of traditional acid-base catalysts.

[0318] (ii) Two sets of experiments were conducted on the degradation of polylactic acid. The only difference between the two sets of experiments was that in one of the experiments, the catalyst diphenyl phosphate was not added (experiment A7). The initial peak molecular weight (M peak ) is 146.8 kDa (gel permeation chromatography test, tetrahydrofuran mobile phase, polystyrene as standard). When a sample is tested by gel permeation chromatography, the molecular weight corresponding to the top of the peak in the elution curve or molecular weight distribution curve is the peak molecular weight (M peak ). The peak molecular weight can be used to preliminarily determine the molecular weight of the polymer.

[0319] (6) Test A6: 0.5 g of polylactic acid PLA and 0.025 g of diphenyl phosphate DPP were placed in a test tube and placed in an oil bath at 160°C. The tube was left uncovered and 2 drops of deionized water were added every 5 min during the reaction. The test time was 0.5 h.

[0320] (7) Test A7: 0.5 g of polylactic acid was placed in a test tube and placed in an oil bath at 160°C. The tube was left uncovered and 2 drops of deionized water were added every 5 minutes during the reaction. The test time was 0.5 h.

[0321] After the reaction started, samples were taken every 5 minutes for testing, and the testing method was the same as before (gel permeation chromatography, tetrahydrofuran mobile phase, polystyrene as standard sample); the peak molecular weight (M) of the products obtained by tests A6 and A7 after 0.5 hours was measured. peak ) are 0.5 kDa and 83.7 kDa respectively. From experiments A6 and A7, it can be seen that even when the amount of water added is small, diphenyl phosphate can still effectively catalyze the degradation of polylactic acid (see Figure 4 ).

[0322] (III) 1 g of PLA pellets (diameter ~3 mm) purchased from TotalEnergies Corbion with the brand name LX175 were placed in 5 different solutions containing 0.035 g of diphenyl phosphate DPP (the mass of the solution was 20 g) at an ambient temperature of 80°C. After 2 days, all the components were taken out and freeze-dried for GPC testing.

[0323] (1) Test B1: Deionized water, GPC test results of freeze-dried sample after 2 days: M n =6.3 kDa, M w =9.1 kDa, PDI = 1.44;

[0324] (2) Test B2: Methanol, GPC test results of freeze-dried sample after 2 days: M n =26.7 kDa, M w =33.1 kDa, PDI = 1.24;

[0325] (3) Test B3: Methanol / water mixed solvent (m / m = 1:3), GPC test results of freeze-dried sample after 2 days: M n =7.4 kDa, M w =10.7 kDa, PDI = 1.45; where m / m represents the mass ratio of the two components;

[0326] (4) Test B4: Methanol / tetrahydrofuran mixed solvent (m / m = 1:3), GPC test results of freeze-dried sample after 2 days: M n =8.6 kDa, M w =13.5 kDa, PDI = 1.57;

[0327] (5) Test B5: Water / tetrahydrofuran mixed solvent (m / m = 1:3), GPC test results of freeze-dried sample after 2 days: M n =0.5 kDa, M w =0.7 kDa, PDI =1.4, the molecular weight of the sample is close to the lower limit of GPC detection.

[0328] From the test B1, it can be seen that polylactic acid can be degraded relatively quickly in the presence of only water and diphenyl phosphate. From the comparison of tests B1, B2 and B3, it can be seen that the degradation rate of polylactic acid in a system with water as solvent is faster than that in a system with methanol as solvent; the degradation rate of polylactic acid in the former system is similar to that in a system with methanol and water as mixed solvents. From the comparison of test B1 and test B5, as well as the comparison of test B2 and test B4, it can be seen that the addition of tetrahydrofuran is conducive to accelerating the degradation rate of polylactic acid. The reason may be that tetrahydrofuran plays a solubilizing role, making the reaction raw materials evenly distributed in the system, increasing the contact and reaction opportunities, thereby accelerating the reaction process.

[0329] (IV) Degradation tests using different polymer materials as substrates.

[0330] 15 g of each of three brands of PLA pellets (all purchased from TotalEnergies Corbion, with brands LX175, LX530 and L105), 10 g of each of two PLA product fragments (purchased from online retail platform (Taobao.com)), and 10 g of each of three common mechanically recyclable durable plastics (polyethylene terephthalate PET, polypropylene PP and polyethylene PE) (purchased from online retail platform (Taobao.com)) were mixed. The mixed plastics included one polyethylene terephthalate PET, one polypropylene PP, one polyethylene PE and five polylactic acid PLA ( Figure 5A). Add 2.275 g of diphenyl phosphate DPP (with a mass ratio of 0.035 to polylactic acid PLA) and 8 g of water to the mixed plastic system, react at 160° C. for 1.5 h and then terminate the reaction; separate the solid matter insoluble in the reaction system from the flowable substance in the product after the reaction, and separate the flowable substance ( Figure 5 The substance contained in the container shown in B) is a degradation product.

[0331] The degradation products ( Figure 5 The substance shown in B) 1 H NMR characterization revealed that the degradation products were lactic acid oligomers and / or monomers with an average molecular weight of 220 Da and an average degree of polymerization of 2.8. No polymers such as PET, PP and PE and their corresponding degradation oligomers and / or monomers were found in the degradation products. Figure 5 C is the solid separated, and the DSC test results of different plastics are respectively carried out and compared with the DSC test results of the corresponding raw materials (PET, PP and PE sheets or pellets) before degradation treatment, that is, Figure 5 D, E and F.

[0332] Through DSC characterization, it can be seen that the melting points (T m ) is basically unchanged: the melting point of PET before treatment is 247.7℃, and the melting point after treatment is 248.1℃ ( Figure 5 D); the melting point of PP before treatment is 161.3℃, and the melting point after treatment is 162.0℃ ( Figure 5 The melting point of PE before treatment is 129.5℃, and the melting point after treatment is 129.6℃ ( Figure 5 F),

[0333] The degradation test on mixed plastics shows that when mixed plastics containing traditional durable plastics and polylactic acid are treated under the aforementioned conditions (i.e., in the presence of water and a specific organic non-metallic catalyst, such as DPP), not only the degradation of degradable polymer materials such as polylactic acid is not affected, but also traditional durable plastics such as PET, PP and PE are not affected by the treatment (no obvious changes are observed in the apparent morphology of PET, PP and PE (see Figure 5 Comparison of A and C), melting point did not change significantly (see Figure 5 D, E and F)) while better maintaining the original performance, and further mechanical recycling of traditional durable plastics PET, PP and PE can be carried out in the future to obtain corresponding recyclates with better quality.

[0334] DSC test method: The thermal properties of plastics are characterized by differential scanning calorimetry (Q2000, TAInstruments). Taking PET as an example, the weighed sample is placed in a sample pan, heated to 320°C in a nitrogen atmosphere, balanced for 5 minutes to remove the thermal history, and then cooled to 20°C at a rate of 10°C / min. After 5 minutes of balancing, the temperature is raised to 320°C at the same rate and the data is recorded. PP and PE are heated to 220°C.

[0335] (V) 5 g of PLA pellets (diameter ∼3 mm) of LX175 purchased from TotalEnergies Corbion were placed in the following three different aqueous solutions (5 g of solution mass) at an ambient temperature of 80°C. 50 mg of the solution was lyophilized 1 day and 3 days after the start of the reaction. 1 H NMR test.

[0336] (1) The first aqueous solution was a 0.1 M (mol / L) HCl solution, in which almost no water-soluble substances were detected. Three days after the reaction began, the system was a suspension with a milky white color.

[0337] (2) The second aqueous solution is an aqueous solution containing 5 wt% diphenyl phosphate DPP. One day after the reaction started, the solution contained lactic acid oligomers and monomers with an average molecular weight of 385 and an average degree of polymerization of 5.1. Three days after the reaction started, the average molecular weight of the degradation product was 108 and the average degree of polymerization was 1.3. At this time, the solution was clear and transparent.

[0338] (3) The third aqueous solution is a 0.1 M (mol / L) HCl solution containing 5 wt% diphenyl phosphate DPP. One day after the reaction started, the solution contained lactic acid oligomers and monomers with an average molecular weight of 167 and an average degree of polymerization of 2.1. Three days after the reaction started, the solution became clear and transparent, and the average molecular weight of the degradation product was 106 and the average degree of polymerization was 1.3.

[0339] The results of the experiments of placing polylactic acid (PLA) in three different aqueous solutions show that, on the one hand, simple HCl cannot effectively catalyze the degradation of PLA; on the other hand, polylactic acid can be degraded relatively quickly in the presence of water and an organic non-metallic catalyst, diphenyl phosphate (DPP). Although the addition of additional hydrochloric acid has a certain accelerating effect on the degradation in the early stage of the reaction, the molecular weight and average degree of polymerization of the degradation products finally prepared are not much different. Therefore, polylactic acid can be degraded relatively quickly in the presence of water and an organic non-metallic catalyst, such as diphenyl phosphate (DPP), without the presence of hydrochloric acid, and can be better recycled.

[0340] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

[0341] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0342] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. A method for regenerating a degradable polymer material, characterized in that: The method comprises the following steps: degrading a degradable polymer material in a system in which an organic non-metallic catalyst and a water-containing solvent exist to obtain a degradation product; in, The degradable polymer material includes one or more of polyester material and polycarbonate material; The organic non-metal catalyst is selected from one or more of diphenyl phosphate, binaphthol phosphate and organic bases, and the organic base is selected from one or more of nitrogen-containing heterobicyclic bases, 4-dimethylaminopyridine and phosphazene base compounds.

2. The regeneration method according to claim 1, characterized in that: The diphenyl phosphate has a structure shown in formula (I): In formula (I), R 11 , R 12 , R 13 , R 14 , R 15 , R 21 , R 22 , R 23 , R 24 and R 25 Each independently selected from any one of -H, halogen, -NO2, C1-C4 alkoxy, C1-C6 alkyl, halogen-substituted C1-C6 alkyl, phenyl, and substituted phenyl, wherein the phenyl ring in the substituted phenyl is substituted by one or more substituents selected from the group consisting of halogen and C1-C4 alkyl; The binaphthol phosphate has a structure shown in formula (II): In formula (II), R3 and R3' are each independently selected from -H, -SiPh3 or Wherein, "*" indicates the attachment site of a covalent single bond; R 41 , R 42 , R 43 , R 44 and R 45 Each is independently selected from any one of -H, halogen, -NO2, C1-C6 alkyl, halogen-substituted C1-C6 alkyl, phenyl, and substituted phenyl, wherein the phenyl ring in the substituted phenyl is substituted by one or more substituents selected from the group consisting of halogen, -NO2, phenyl, and C1-C4 alkyl; or R 41 , R 42 , R 43 , R 44 and R 45 At least two of them form a ring and participate in forming a fused ring, R 41 , R 42 , R 43 , R 44 and R 45 The uncyclic groups are each independently selected from any one of -H, halogen, -NO2, C1-C6 alkyl, halogen-substituted C1-C6 alkyl, phenyl, and substituted phenyl, wherein the phenyl ring in the substituted phenyl is substituted by one or more substituents selected from the group consisting of halogen, -NO2, phenyl, and C1-C4 alkyl; The nitrogen-containing heterobicyclic base is selected from the group consisting of: In formula (III), Y is -CH2-, -NH- or -N(CH3)-; n is 1 or 2; The phosphazene base compound has a structure shown in formula (IV): In formula (IV), R is halogen, C1-C4 alkyl or C1-C4 alkoxy.

3. The regeneration method according to claim 1, characterized in that: Satisfy one or more of the following characteristics: The number average molecular weight of the degradable polymer material is 10 kDa to 250 kDa; The mass ratio of water to the degradable polymer material in the system is (0.01-10):1; The mass ratio of the organic non-metallic catalyst to the degradable polymer material is (0.001-0.1):1; The average degree of polymerization of the degradation product is ≤20.

4. The regeneration method according to claim 1, characterized in that: Satisfy one or more of the following characteristics: The degradable polymer material is selected from one or more of polylactic acid, polyglycolic acid, polyε-caprolactone, polylactic acid-glycolic acid copolymer, polyglycolic acid-ε-caprolactone copolymer, polylactic acid-ε-caprolactone copolymer, polyδ-valerolactone, polybutyrolactone, polybutylene succinate, polybutylene adipate / terephthalate, polyhydroxyalkanoate and polytrimethylene carbonate; The diphenyl phosphate catalyst is selected from one or more of diphenyl phosphate, bis(4-nitrophenyl)phosphate and bis(2,6-dimethylphenyl)phosphate; The binaphthol phosphate catalyst is one or more of binaphthol phosphate, R-binaphthol phosphate, R-3,3'-bis(triphenylsilyl)binaphthol phosphonate and R-3,3'-bis(2,4,6-triisopropylphenyl)binaphthol phosphonate; The organic base catalyst is selected from 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,5,7-triazidobicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 4-dimethylaminopyridine, tert-butylimino-tris(dimethylamino)phosphorane, 1-tert-butyl-2,2,4,4,4-penta(dimethylamino)-2Λ5,4Λ5-bis(phosphorus nitrogen-based compound) and cyclotriphosphazene base and 1-tert-butyl-4,4,4-tris(dimethylamino)-2,2-bis[tris(dimethylamino)-phosphoranylideneamino]-2Λ5,4Λ5-bis(phosphorus nitrogen-based compound) One or more.

5. The regeneration method according to claim 1, characterized in that: The following steps are involved: In the system where the organic non-metallic catalyst and the aqueous solvent exist, subjecting the first degradable polymer material to a first degradation treatment to obtain a first degradation product; The i-th degradation product and the i+1-th degradable polymer material are mixed, and the i+1-th degradation treatment is performed to obtain the i+1-th degradation product, wherein i is an integer ≥1, and the i+1-th degradable polymer material includes at least the second degradable polymer material; the degradation treatment is terminated when i+1=n to obtain the n-th degradation product, wherein n is an integer ≥2, and the average degree of polymerization of the n-th degradation product is ≤20.

6. The regeneration method according to any one of claims 1 to 5, characterized in that: Satisfy one or more of the following characteristics: The temperature of any degradation treatment is independently 125°C to 200°C; The time of any degradation treatment is independently 0.25h to 5h; The pressure of any degradation treatment is independently 100±5 kPa.

7. The regeneration method according to any one of claims 1 to 5, characterized in that: The following steps are also included: The degradation product is washed with an organic solvent; wherein the organic solvent is selected from one or more of chloroform, petroleum ether, carbon disulfide, ether, dichloromethane, benzene, toluene and ethyl acetate.

8. A low molecular weight composition, characterized in that The low molecular weight composition is a degradation product of a degradable polymer material, and the low molecular weight composition is prepared according to the regeneration method according to any one of claims 1 to 7, wherein the average polymerization degree of the low molecular weight composition is ≤20.

9. A method for recycling degradable polymer materials, characterized in that: The following steps are involved: A polymerization reaction is carried out using a low molecular weight composition as an initial raw material; wherein the low molecular weight composition is a degradation product prepared by the regeneration treatment method described in claims 1 to 7 or the low molecular weight composition described in claim 8.

10. Application of organic non-metallic catalysts in the degradation of degradable polymer materials; in, The organic non-metallic catalyst and the degradable polymer material are as defined in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Alcoholysis recovery method of waster polylactic acid in ionic liquid environment

    CN102659590A

  • Alcoholysis method for liquid lewis acid catalyst to catalyze waste polylactide material

    CN105017013A

  • Method for catalytic alcoholysis of PLA (Polylactic Acid) by CaO / MCF (Mesocellular silica Foam) mesoporous basic molecular sieve

    CN107382718A

  • Catalyst capable of performing alcoholysis on polylactic acid and method

    CN108837847A

  • Method for recovering methyl lactate by using supported ionic liquid for catalyzing alcoholysis of waste polylactic acid

    CN110003009A

Cited By

  • Method and system for recycling glycollic acid

    CN122608504A